GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 782782893 species occurrences available in GBIF matching the query: All data. The dataset includes 782782893 records from 16862 constituent datasets: 1289 records from RECORD Orthoptera Data. 1715185 records from NBIS Records to December 2016. 8 records from Sandsitermes gen. nov., a new nasute termite genus from South America (Isoptera, Termitidae, Nasutitermitinae). 2494 records from Colección de peces dulceacuícolas de Costa Rica. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 1 records from Oribates calcaratus. 1704 records from Estructura poblacional, variación genética y conservación de tres especies del género Pinus, endémicas de México. 4303 records from Odonata Collection. 8857 records from Artròpodes d'Andorra. 1 records from Simulium (Gomphostilbia) lemborense, a new black fly species (Diptera: Simuliidae) from Flores, Indonesia. 761 records from Finchingfield Brook historic river corridor surveys. 29 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 5414 records from Ontario BioBlitz Species Records. 71 records from (Data S1) Palynology of ODP Site 113-696. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 1000 records from Lichens along norwegian rivers. 1 records from Waldtag in und um Seelingstädt. 126 records from Total foraminifera counts from M35/1_MSN1050. 17618 records from BioGIS - Mammals - INPA database. 13 records from A new species of Eigenmannia Jordan and Evermann (Gymnotiformes: Sternopygidae) from the upper rio Paraguai basin. 7 records from A review of Japanese species of Allophrys Förster (Hymenoptera: Ichneumonidae: Tersilochinae). 600083 records from RECORD Aves Data. 8 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Ardgour Pinewoods SSSI. 6 records from Wiese. 558 records from (Table 5) Pleistocene ostracodes from ODP Hole 104-644A. 2268 records from Ictiofauna de los corredores biológicos Sierra Madre del Sur y Selva Maya Zoque. 274 records from Foraminifera abundance of sediment core BM1958.631. 320 records from Range table from planktonic foraminifers in ODP Hole 141-863A. 769 records from Range table from benthic foraminifers in ODP Hole 145-883B. 48243 records from Millipede (Diplopoda) records for Britain and Ireland to 2005. 64 records from City of Edinburgh Natural Heritage Service - Common Blue & Six Spot Burnet Moth Survey. 3204 records from Faunal Inventory of Morysin Nature Reserve. 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 133 records from Schellenberg A. 1936. The fishery grounds near Alexandria. 10. Amphipoda Benthonica. Notes and memoirs no 11. 3 records from A new species of Lyssomanes Hentz, 1845 from Brazil (Araneae: Salticidae). 2955 records from Change in aboveground biomass carbon stock following the establishment of exclosures on degraded lands in Tigray, Ethiopia. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 311 records from Genotipificación de especies de la ictiofauna del Sistema Pánuco-Tamesí a través de la generación del código de barras de ADN mitocondrial. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 13 records from FND "Weißer Berg" Leißling. 95 records from BIRDRACE BiBi. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 138 records from Total foraminifera counts of multinet M10/2_MSN297. 156 records from Dinoflagellate cysts of mooring MST-9 (station 915) with cell content. 49 records from Pollen profile form Hickory Ridge Basin, Illinois, U.S.A. 209 records from Relative abundance of coccosphere-units at site GIK23414. 21 records from Nannofossil abundance of Hole 6-55. 3 records from Nannofossil abundance of Hole 31-301. 3 records from Nannofossil abundance of Hole 94-609A. 3 records from Microfossil abundance of Hole 50-415. 64 records from Six new Brazilian species of Polana (Varpulana) (Hemiptera: Cicadellidae: Gyponini) with key to males. 11 records from Zoobenthos in surface sediments off Cape Lucul. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 16 records from Coccolith counts of multinet M32/5_MSN986. 451 records from Nannofossil abundance of Hole 15-148. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/090-4. 131 records from (Table 3) Occurrence of benthic foraminifera in the Ledyanaya section. 216 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE236. 1972 records from (Figure 6) Distribution chart of benthic foraminifers in ODP Site 126-792. 1691 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 15972 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 423 records from Bird Collection of Otto Hedin. 97 records from CNIN/Tipos Hymenoptera. 313949 records from United States National Plant Germplasm System Collection. 117 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 3 records from Analyses of the recent components of sediment core PS1215-2. 169 records from Whale log - observations from ANARE voyages. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/046-3. 818 records from Range chart of calcareous nannofossils from ODP Hole 188-1165B (Table 1). 3910 records from Plant (MNHM-PL). 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 1218 records from (Table 6) Relative abundances of the seven species of planktonic foraminifera from ODP Site 108-662. 2427 records from Ibaraki Nature Museum, Mollusk collection. 75655 records from Ibaraki Nature Museum, Vascular Plants collection. 15586 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 109504 records from Plant Specimens of Kurashiki Museum of Natural History. 13225 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 12 records from Abundance of microplankton from bottle APRIL-2000-K4. 19 records from Occurrence of mammalia relicts at site Gröbern. 108 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 68 records from Planktic foraminifera abundance of Hole 22-213. 126 records from Planktic foraminifera abundance of Hole 32-305. 176 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 1505 records from Relative abundance of planktonic foraminifera in Pliocene and Pleistocene sediments of DSDP Hole 32-310 from Hess Rise, Central North Pacific (Table II). 780 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 646 records from Engraulidae-Clupeidae. Report on the Danish Oceanographical Expeditions 1908-1910 to the Mediterranean and adjacent seas. 48 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 1 records from Occurrence of mammalia relicts at site Kleine Feldhofer Grotte. 164 records from Planktic foraminifera abundance of Hole 22-215. 26 records from Planktic foraminifera abundance of Hole 20-200A. 1 records from Redescription of the numbat tick Ixodes (Sternalixodes) myrmecobii Roberts, 1962 (Acari: Ixodidae) with descriptions of the male and nymph, and new host records. 5 records from Two new endemic species of Epictia Gray, 1845 (Serpentes: Leptotyphlopidae) from Northern Peru. 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 162150 records from Ditsong National Museum of Natural History Collection: 1805-2008. 20 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2004. 496 records from 2000-2003 RBWM WHS Surveys. 93 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cotingidae. 4 records from Revision of Continental African Germalus (Heteroptera: Lygaeoidea: Geocoridae). 8 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Abbey Craig SSSI. 1798 records from Insect (KIDR-IN). 2 records from Abundance of benthos infauna at station GIK23025-2. 89762 records from Ornitho.eus. 45 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 2895 records from Estudio de la fauna edáfica en una selva baja inundable de la Reserva de la biósfera de Sian Ka'an Quintana Roo. 1 records from Zetes latirostris. 113 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 627 records from Inventario forestal en bosques dominados por encino (Quercus Fagaceae) en la Sierra de Manantlán, Jalisco-Colima, México: Descripción de los patrones de respuesta al medio físico y biológico. 1849 records from Heigham Holmes species data held by The National Trust. 8 records from Pollen analysis of sediment profile BUA1 from Buchsee. 101 records from MVZ Mammal Observations (Arctos). 14 records from Contribution to the knowledge of Neoperla (Plecoptera: Perlidae) from Hainan Province of China. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 11 records from Three new species and redescription of the type species of Soesilarishius Makhan, 2007 (Araneae: Salticidae: Euophryini). 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 61 records from Fürstenberger Ralley Teil 3. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 160 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 255 records from City of Edinburgh Natural Heritage Service - Natural Heritage Service Data. 7 records from Two new species of Trimma (Pisces; Gobiidae) from Fiji, south-western Pacific Ocean. 1207 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 177466 records from CAS Entomology (ENT). 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 1565 records from Inventarios florísticos en Baja California Sur (II): Vegetación costera. 117 records from Wassermann. 73 records from VFD-HH/SH: Pferdweide Lammert. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 1770 records from Schmidt Museum of Natural History_Birds. 128 records from Total foraminifera counts of multinet M33/1_MSN1030. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 110 records from Abundance of planktic foraminifera at CTD station M39/4_366CTD-22. 54 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211660-6. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1. 22 records from Phytoplankton abundance at bottle station GOM6/1. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 45 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 374 records from Diversidad y distribución del género Tripsacum (Poaceae: Tripsacinae) en México. 16 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 3594 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 81 records from Umgebung des Spalatin Gymnasium Altenburg. 105 records from BIRDRACE coesfelder_vogelkundler. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 88 records from Upper Aptian Niveau Kilian range chart of nannofossils in SE France. 10 records from Benthic macrofauna abundance of sediment core 13078-017. 114 records from Contribution to the knowledge of the genus Singilis Rambur, 1837 of Africa (Coleoptera: Carabidae: Lebiini). Part IV. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 16425 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 5233 records from (Appendix A) Stable carbon and oxygen isotopes and paleoproductivity reconstructions for the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 46 records from An der Ohm, (Wettsaasen). 1 records from Occurrence of mammalia relicts at site Ballybetagh. 1351 records from Neogene palynomorpha from site 93-603, part 1. 525 records from Planktic foraminifera abundance of Hole 94-609. 283549 records from USGS Great Lakes Science Center Research Vessel Catch Information System Trawl. 2259 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/009-2. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 18 records from Meiofauna abundance in sediment core 13368-015. 308 records from Planktic foraminifera counts of sediment core V19-178. 106100 records from Fish (NSMK-PI). 234 records from Phytoplankton samples - 2006/07 V3 SAZ-Sense. 1 records from Zetes semirufus. 1860 records from Importancia de las lombrices de tierra (Oligochaeta) en el monitoreo de áreas prioritarias de conservación del centro, este y sureste de México. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 535 records from Distribution of microorganisms in recent sediments of Kiel Bay. 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 31082 records from MEXU/Plantas Vasculares. 8980 records from MEXU/Tipos de plantas vasculares. 82953 records from Vascular Plants, Observations, Oslo (O). 877 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987). 257 records from Kernberge und Umgebung (Jena). 17 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 28 records from Occurrence of mammalia relicts at site Climauti II. 2880 records from Coleoptera, NEF. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/508-2. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-070. 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 43590 records from Computarización de la colección de abejas (Hymenoptera: Apoidea) del Museo de Zoología Alfonso L. Herrera, de la Facultad de Ciencias de la UNAM. 29 records from Klimaoasen in Köln. 83 records from Planktic foraminifera abundance of Hole 14-135. 2357 records from Foraminifera abundance of Hole 17-167. 12 records from Abundance of epibenthic echinoderms at seafloor photography station M21/5_317. 163418 records from Etapa final de la captura y catalogación del Herbario del Instituto de Ecología, AC, Centro Regional del Bajío. 161 records from A conspectus of the native and naturalized species of Nephrolepis (Nephrolepidaceae) in the world. 31 records from Description of a new species of Acestridium (Siluriformes: Loricariidae) from Colombia.. 284 records from Filogeografía y recursos genéticos de las vainillas de México. 1 records from Contribution to the Uropodina mites of Peru (Acari: Mesostigmata). 1494 records from CSIRO, Cruise SS200001, Marine Biodiversity, South and Southeast Australia, 2001. 280 records from (Figure 1d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3202. 3 records from The dark side of pumpkin toadlet: a new species of Brachycephalus (Anura: Brachycephalidae) from Serra do Brigadeiro, southeastern Brazil. 1 records from Miriapodi di alcune grotte della Campania. 305 records from Camera trap database of Tiger from Rajaji National Park, Uttarakhand. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 1 records from Planktic foraminifera abundance of Hole 8-72. 163 records from Planktic foraminifera abundance of Hole 32-313. 3119 records from Hormigas en cultivos de naranja (Citrus sinensis (L.) Osbeck) de la costa Caribe de Colombia. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 70 records from Exotic terrestrial flatworms, Macquarie Island. 34140 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 80 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 1. 9 records from Canthyporus reebae sp. nov. from the Itremo and Andringitra mountains of central eastern Madagascar (Coleoptera: Dytiscidae: Hydroporinae). 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 2403 records from ZUEC-AVE - Coleção de Aves do Museu de Zoologia da UNICAMP. 38 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 30 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 2 records from The Genus Criodion (Audinet-Serville, 1833) (Coleoptera, Cerambycidae): First Record for Panama. 59 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 1639 records from Avena wild species collection. (N.I.Vavilov Institute of Plant Genetic Resources (VIR)). 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 27 records from City of Edinburgh Natural Heritage Service - Small Pearl-bordered Fritillary Survey. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 261826 records from R. L. McGregor Herbarium Vascular Plants Collection. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 3513 records from MPM Milwaukee Public Museum Invertebrate Zoology Collection. 347088 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 1116766 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 16 records from Revisions of two poorly known species of Opisthotropis Günther, 1872 (Squamata: Colubridae: Natricinae) with description of a new species from China. 403 records from (Appendix A) Relative abundance of Emiliania huxleyi in sediment cores of the North Atlantic. 235202 records from MVZ Mammal Collection (Arctos). 289 records from Arizona State University Charles O'Brien Collection. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 3953 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 31 records from Stalked jellyfishes (Cnidaria: Staurozoa) of South Africa, with the description of Calvadosia lewisi sp. nov.. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 20 records from Ecología de jaguares y pumas en el oeste de México: Fase II. 2 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 15 records from AKG-Bensheim. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 178 records from Total foraminifera counts of multinet M6/7_MSN148. 9179 records from Fiocruz/CTIOC - Coleção de Triatomíneos do Instituto Oswaldo Cruz. 4872 records from Abundance and diversity of the Amphipoda (Crustacea) from the Greenlandic shelf. 76 records from Caracterización Floristica del Páramo Tatamá. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1995 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 26 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 2 records from Description of a new genus and two new species of alpheid shrimps from Guam (Crustacea, Decapoda) *. 39 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part III. Genera Camptochaeta Hippa & Vilkamaa, Claustropyga Hippa, Vilkamaa & Mohrig and Dichopygina Vilkamaa, Hippa & Komarova. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 101 records from Birdrace-Herford-Birder-Herford. 881 records from Moluscos Marinhos de Augusto Nobre. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 3000 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 3860 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 478 records from Chinese species of Pediobius Walker (Hymenoptera: Eulophidae). 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 10 records from On the spider genus Arboricaria with the description of a new species (Araneae, Gnaphosidae). 119366 records from The digitization of plant specimens of NTU. 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 196124 records from Field Museum of Natural History (Zoology) Mammal Collection. 2 records from Amphibia ZMK. 5 records from A new genus and species of Neotropical Nemobiinae (Insecta: Orthoptera: Grylloidea: Trigonidiidae: Nemobiinae). 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 35 records from Gym Freyung. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 443 records from NE Scotland mollusc records 1800-2010. 26 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 100 records from (Table 4) Distribution of nannofossils in DSDP Hole 87-583D. 501 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-075. 182 records from Polychaeta Orbiniidae from Antarctica, the Southern Ocean, the Abyssal Pacific Ocean, and off South America. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 463 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 210 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 1968 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518. 1 records from Results of palynological analysis of Hole 302-M0004C. 89 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (75° N section). 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 1092 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 4 records from Tropidomyrmex elianae, a new myrmicine ant genus and species from Brazil, tentatively assigned to Solenopsidini (Hymenoptera, Formicidae).. 73 records from Fossil (JNHM-FO). 32450 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions. 2 records from Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae). 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 1 records from The taxonomic status of two Telmatobius frog species (Anura: Telmatobiidae) from the western Andean slopes of northernmost Chile. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 114 records from BIRDRACE VIE will rock you!. 10 records from Benthic macrofauna abundance of sediment core 12930-044. 68784 records from Birds (KIEE-BI). 241 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 84 records from Museu Paraense Emílio Goeldi - Myriapoda Collection. 18822 records from Mycology herbarium, NTNU University Museum. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 14202 records from Plant specimens of Hokkaido University Museum. 1115 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 1161 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 398 records from Mooswald (Freiburg). 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 16 records from Redescriptions and new host records of chewing lice of the genus Ricinus (Phthiraptera: Ricinidae) from the Neotropical Region. 53 records from Planktic foraminifera abundance of Hole 29-281A. 102 records from Range table from planktonic foraminifers in ODP Hole 169-1035D. 899 records from (Fig. 13) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 80-549 in the North Atlantic. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 200 records from HeathNet data. 11 records from Collection Xiphosura SMF. 3664 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 734 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Icteridae. 1340 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 13736 records from MfN - Mallophaga Collection. 37641 records from Nordic Genetic Resources. 3634 records from Herpetological collection of National Museum of Nature and Science. 13478 records from Herp Collection. 66 records from Foraminifera abundance of Hole 55-432A. 30 records from Benthic foraminifera abundance of Hole 42-379A. 401 records from Range table from planktonic foraminifers in ODP Hole 138-852B. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 30 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 10121 records from Arachnologie - SMNG. 27 records from Bearded Tit National Survey in Britain 1992. 3711 records from Florida Keys Reef Visual Census 2004. 10978 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 4 records from New littoral mite species (Acari, Oribatida, Fortuyniidae) from the Galápagos archipelago, with ecological and zoogeographical considerations. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 224432 records from Some Plant Specimens from PE Herbarium in China from 1900 to 1950. 75 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 164 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 269 records from BIRDRACE Dithmarscher Deichhühner. 22625 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 2573320 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 37 records from Checklist, new species and new records of Cerambycidae (Insecta: Coleoptera) from Chapada Diamantina, Bahia state, Brazil. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 1 records from Zetes ephippiatus. 449 records from Artsprosjekt Pyrenomycetes. 2 records from Two new Neotropical species of Djalmabatista Fittkau (Diptera: Chironomidae). 906 records from Digital Florula - Las Cruces Biological Station. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 20146 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán. 18247 records from Base de datos del Herbario CIQR de El Colegio de la Frontera Sur, unidad Chetumal. 97 records from LauWi. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 72 records from Faunal assemblage of sediment core TR149-35. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 105 records from Plasm bearing foraminifera counts of multinet M21/5_MSN731. 92 records from Total foraminifera counts of multinet M26/1_MSN845. 1 records from Notizen über Oribatei (Acari). III. 3 records from A new species of the genus Meganola Dyar, 1898 (Lepidoptera, Nolidae, Nolinae) from China. 6250 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 1472 records from Estudios previos justificativos para la declaratoria de áreas naturales protegidas en Tamaulipas. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 38 records from What is Tetramoriumsemilaeve Andre, 1883? (Hymenoptera, Formicidae). 10 records from Ice Amphipods Canada Basin. 12 records from Taxonomic notes on the genus Protanilla (Hymenoptera: Formicidae: Leptanillinae) from Taiwan. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 20 records from Mikroorganismen. 48 records from Wahner Heide LK 12 Biologie. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 2233 records from Chrysomelidae of Poland. 135 records from Total foraminifera counts of multinet M11/1_MSN522. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_13-CTD162. 2 records from Kirchenforst. 30 records from Nannofossil abundance of Hole 8-71. 6 records from Benthic macrofauna abundance of sediment core 13077-019. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 271 records from Planktic foraminifera counts of sediment core RC11-147. 67 records from (Table 5) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-9. 64 records from Feuchtbiotop Weidenkaule. 21 records from Nannofossil abundance of Hole 24-232A. 18 records from Benthic macrofauna abundance of sediment core 13201-002. 51 records from (Table 8) Percent distribution of calcareous nannofossils at ODP Hole 125-781A. 2612 records from Flora genérica de las gramíneas del estado de Tlaxcala. 7076556 records from Great Backyard Bird Count. 22 records from Sediment properties of core PLG95B_06BOXG. 448 records from Harpactus Shuckard. 131 records from Unser Schulhof - eine Apotheke. 48 records from Freiheitsring (Frechen). 241 records from Planktic foraminifera abundance of Hole 67-499B. 54 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 30 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-913B. 15 records from Two new species of Huascaromusca Townsend from Colombia, and a new combination for Giovanella carvalhoi (Diptera: Mesembrinellidae). 1 records from A NEW SPECIES OF DRY FOLIAGE MIMICKING Eriovixia ARCHER, 1951 FROM CENTRAL WESTERN GHATS, INDIA (ARANEAE: ARANEIDAE). 4 records from Two new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 2775 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 354 records from Sponges of the Guyana Shelf. 49 records from Additional records for Stenosagola newtoni Park & Carlton, 2013 (Staphylinidae: Pselaphinae: Faronitae), with notes on aedeagal morphology. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 133 records from Total foraminifera counts of multinet PO247/2_MSN1381. 47 records from Foraminifera species abundances from tow TT007_3-MOC6. 569 records from (Appendix A) Planktonic foraminiferal abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 4 records from Counts (3) of calcareous dinocysts along profile Stevns-Klint. 8 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-06-2. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 246 records from Stoats in Orkney Facebook page records & sightings, 2014 - 2015. 1726 records from KTU Pinophyta. 22 records from Nannofossil abundance of Hole 9-83A. 115 records from Nannofossil abundance of Hole 29-279A. 9 records from Nannofossil abundance of Hole 60-455. 56 records from Nannofossil abundance of Hole 94-607. 81 records from Colección de Referencia de Poliquetos del Museo de Ciencias de la Universidad El Bosque. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-087. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 9852 records from ZUEC-LEP - Coleção de Lepidoptera do Museu de Zoologia da UNICAMP. 4 records from Description of three liocranid spider species from Korea (Araneae: Liocranidae). 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 1496 records from (Table 4) Distribution of planktonic foraminifers in ODP Hole 108-658A. 176 records from paleovertebrados. 2019 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 2070 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 24 records from Ficha de Sonora aemula. 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 998 records from Korean Ethnobotany Database. 61234 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 5159 records from CNHE/Coleccion Nacional de Helmintos. 342 records from (Table A.10) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (150-500 µm). 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 90 records from Schulhof Bühlschule Giengen. 67 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 73 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 9 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (2000m section). 57 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tityridae. 3941 records from UAFMC Mammals. 1069 records from ZFMK Sound Archive. 52 records from Coleção de Ascidiacea do Museu Nacional - UFRJ. 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 5424 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 3761 records from Mountain Invasion Research Network (MIREN) survey. 30302 records from Arizona State University Amphibian and Reptile Collection. 11708 records from The Erysiphales Collection at the Botanische Staatssammlung München. 195264 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 5 records from Analyses of the recent components of sediment core PS1400-4. 2128 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 40316 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - non-sensitive species. 34 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 2945 records from (Figure 4) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Site 71-512. 1142 records from Range table from planktonic foraminifers in ODP Hole 154-925A. 1741 records from Benthic foraminifera abundance of Hole 84-570, Part 1. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 13 records from Collection Reptilia fossil SMF. 606 records from MODIRISK:Monitoring of Mosquito Vectors, Longitudinal study. 1008 records from zooplankton and phytoplankton interactions. Northeast Greenland 2013. 31129 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 2324 records from Eriophyoid Mites of Poland. 836971 records from Bernice P. Bishop Museum. 355 records from Cuarenta y ocho especies de la flora de Chiapas incluidas en el PROY-NOM-059-ECOL-2000. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 170 records from Thistles and numbers of observed invertebrates, fungi and damage types. 833 records from Marine data from The Wildlife Trusts (TWT) Dive Team; Somerset, Cornwall and Sussex; 2014-2015. 22876 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 1761 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 3642 records from Algae, Specimens, Agder naturmuseum (KMN). 5733 records from Small Mammal Research Database. 83 records from Fiocruz/COLPROT - Coleção de Protozoários. 320488 records from Entomology, Natural History Museum, University of Oslo. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 6181 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 53 records from SNH Invertebrate Site Condition Monitoring 2015: Maidens to Doonfoot SSSI. 39385 records from SAEON: Historical Research Survey Database (1897-1949). 84521 records from BioGIS - Vascular plants - INPA database. 160 records from Wirbach-Taubental (Bad Blankenburg). 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 103 records from BIRDRACE Die Otzberger. 84 records from BIRDRACE Birding for Nature. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 683 records from Lama Forest reserve Inventory, South Benin. Data published in the framework of JRS Benin project. 3 records from Systematics of a small Gehyra (Squamata: Gekkonidae) from the Einasleigh Uplands, Queensland: description of a new range restricted species. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 98423 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 1728 records from CASES: The pre-winter assemblages of southeastern Beaufort Sea. 66028 records from Kathryn Kalmbach Herbarium. 48 records from Trockenrasen bei Dörndorf. 47 records from Schulgelände Ceciliengymnasium. 186 records from Total foraminifera counts of multinet M21/1_MSN604. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_5-CTD56. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/107-5. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 566 records from (Appendix A1) Distribution of benthic foraminifera in ODP Site 184-1143. 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 43 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV30_1. 32825 records from National fish tag database. 168 records from Weidenhüttendorf an der Würm (München). 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 372 records from Colección de Entomología - Arthropoda. 8 records from New taxonomic, stratigraphic, and geographic information on the genus Faksephyllia Floris, 1972 (Scleractinia; Caryophylliidae); first records from the Oligocene of Austria, Germany, and Italy. 48 records from Distribución, abundancia, estructura poblacional y potencial reproductor de Zamia furfuracea L.. 21 records from New species of the genus Gnathochorisis Förster (Hymenoptera: Ichneumonidae: Orthocentrinae) from the Neotropical Region. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 135 records from Total foraminifera counts of multinet M21/3_MSN688. 23 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5136-1. 170 records from The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 2268 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 6 records from Phytoplankton abundance at station Rigel_1_2005-03 in March 2005, Chipana, Chile. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 7 records from Abundance of nematoda in sediment profile M3/1_029 from the Iberian deep sea basin (Table 5). 70 records from Parkuntersuchung Weißer See. 94 records from Coccolith counts of multinet SO119_MSN1298. 482 records from Total foraminifera counts of multinet M6/7_MSN91. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 21 records from Phytoplankton abundance at the sea bottom off Sechura in january 2007, Peru. 19 records from Nannofossil abundance of Hole 31-298. 57 records from Nannofossil abundance in sediment core PS1311-4. 1191 records from Relative abundance of Neogene nannofossils at ODP Site 138-850 from the eastern equatorial Pacific. 315 records from Planktic foraminifera counts of sediment core RC17-69. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 422 records from EA Protected Species Database Desmoulin's whorl snail. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 708 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 35 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cadder Wilderness SSSI. 5512 records from Vascular Plants Collection of National Museum of Nature and Science. 48700 records from Museu Paraense Emilio Goeldi - Ophidia Collection. 302 records from Stadtpark Sulzbach-Rosenberg. 195 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 2 records from Occurrence of mammalia relicts at site Dechenhöhle. 1 records from Planktic foraminifera abundance of Hole 54-420A. 774 records from Planktic foraminifera abundance of Hole 80-549A. 6 records from Nannofossil abundance of Hole 7-63. 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 334 records from Listado florístico y etnobotánico de las plantas medicinales de los huicholes del río Chapalagana, Jalisco y del Nayar, Nayarit. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 47 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 1541 records from (Appendix B3) Calcareous nannofossils of ODP Site 208-1263. 93 records from CCUG Microorganisms databases(Fungi). 17980 records from Impetus - Herbarium Hamburgense. 318 records from Nematode abundance in cold seep sediments of the Darwin mud volcano. 66298 records from Bosque Mesófilo de Montaña de México. 311 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 1 records from Nothrus biverrucatus. 106 records from Anfibios y reptiles de la sierra de Cuatro Venados, Oaxaca, México. 14 records from Clarification of Einfeldia Kieffer, 1922 (Diptera: Chironomidae) with E. australiensis (Freeman, 1961), comb. n. based on immature stages. 51511 records from IMOS - AusCPR: Zooplankton Abundance. 8 records from A revision of the genus Lepidobrya Womersley (Collembola: Entomobryidae) based on morphology and sequence data of the genotype. 67 records from A new species of habitat – forming Suberites (Porifera, Demospongiae, Suberitida) in the Benguela upwelling region (South Africa). 76 records from Coccoliths in sediment core PS1533-3. 1551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 9 records from (Table 2) Macrobenthos on the floor of the West Bay of the Furugelm Island, Sea of Japan. 109176 records from Herps Specimens. 1028827 records from SEAMAP - marine mammals, birds and turtles. 54059 records from Pelagic Fish Observations 1968-1999. 6 records from Sediment properties of core PLG93_BCORE1. 154 records from Planktic foraminifera distribution of sediment core TRI171-27. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 97 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 778 records from Planktic foraminifera abundance of Hole 40-362. 57 records from Range table from planktonic foraminifers in ODP Hole 152-915A. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2571 records from Black grouse annual lek surveys in Dumfries and Galloway, 1980-2011. 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 4051 records from Homoptera. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 862 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 2 records from New data on the rare Afrotropical scarab beetles Orphnus drumonti Frolov and Delopleurus naviauxi Frolov et Cambefort (Coleoptera, Scarabaeidae, Orphninae and Scarabaeinae). 1893 records from Yeast Collection in BCRC. 11 records from Biology and Ecology of Cryopelagic Amphipods from Arctic Sea Ice Collected near Franz Josef Land in the summer of 1994. 3947 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 1709819 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 55 records from Additions and corrections to the systematics of mayfly species assigned to the genus Callibaetis Eaton 1881 (Ephemeroptera: Baetidae) from South America. 5 records from Two new species of Diastatotropis Lacordaire (Coleoptera: Anthribidae) from east Madagascar with a key to species of the genus. 588 records from Relative abundance of ostracods in sediment core Lz1120. 8 records from Lathrolestes Förster, 1869 (Hymenoptera, Ichneumonidae) from Brazil, with description of two new species and a key to the Neotropical species. 235 records from Total foraminifera counts from multinet M31/3_MSN905. 217 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 5638976 records from UK Butterfly Monitoring Scheme (UKBMS). 1731 records from (Figure 3) Range of selected planktonic foraminifera in Paleocene samples of DSDP Hole 93-605. 1156 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 2471 records from Diversidad fúngica en planicies del desierto central sonorense y centro del desierto chihuahuense. 14 records from Two new species of Stenaelurillus Simon, 1886 from India (Araneae: Salticidae: Aelurillina). 19 records from Three new Scandinavian species of Culicoides (Culicoides): C. boyi sp. nov., C. selandicus sp. nov. and C. kalix sp. nov. (Diptera: Ceratopogonidae). 6062 records from Lichens of Knyszyn Forest. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 8858 records from (Appendix 2a) Foraminiferal analyses of research borehole Sonder Vium. 66 records from Mammals (KIEE-MM). 18 records from Black grouse lek survey in Lothian and Borders, 2008. 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 5549 records from Diplopoda (NSMK-DI). 7 records from New species and new behavioral data of Phlugiola Karny, 1907 (Orthoptera: Tettigoniidae: Meconematinae) from the Brazilian Amazonian Rainforest. 78 records from Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula. 22 records from Cryptic diversity within the narrowly endemic Lerista wilkinsi group of north Queensland—two new species (Reptilia: Scincidae). 43066 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 771 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from Type designations and taxonomic remarks for Nearctic sap beetles in the subfamily Carpophilinae Erichson (Coleoptera: Nitidulidae). 32 records from Billards A. 1936. Les fonds de peches pres d Alexandrie. VI Hydroidea. Notes et memoires No 24. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 536 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1201 records from Monocotyledonous Geophytes of Fergana Valley. 597 records from Collection Crustacea - KAUMM. 158 records from Distribución actual, estatus poblacional y evaluación del estatus de protección del pavo ocelado (Agriocharis ocellata). 1512 records from tree climbing bryophytes & lichens at tree base and crown with traits. 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 1 records from Zetes cespitum. 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 77 records from Inhaltsstoffe_Blattmischproben_2008. 74 records from SuLaMa reptile monitoring. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 107 records from BIRDRACE Herford Birders. 195 records from Total foraminifera counts from multinet M31/3_MSN923. 85 records from Plasm bearing foraminifera counts from M35/1_MSN1053. 59 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/424-22. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 12 records from Abundance of radiolaria at station LV28-40-2. 1 records from Hausgarten. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 14 records from Benthic macrofauna abundance of sediment core 12930-093. 86 records from Fliegenhaupt Marksuhl. 141 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-115BX. 441 records from Pollen analysis of surface samples from Germany and Austria. 25471 records from Ibaraki Nature Museum, Arthropoda collection. 886 records from Lepidoptera Observations from New Zealand by Donald Hobern. 40 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1). 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 320 records from Myxomycetes collection of the University of Eastern Finland. 52920 records from West African Vegetation Database. 353 records from Planktic foraminifera distribution of sediment core GIK17940-2. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1217-1. 88 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 96 records from Range table from planktonic foraminifers in ODP Hole 182-1126D. 81 records from Range table from benthic foraminifers in ODP Hole 172-1061C. 1 records from Pollen and spore abundance of Hole 42-379A. 2 records from The second species of Phanoperla (Plecoptera: Perlidae) from China, P. hainana sp. nov., from Hainan Island. 6 records from New records of Indian Nematomorpha, with the description of a new species from the genus Chordodes. 492 records from Verneplan Hjerkinn karplanter. 102 records from A new species of snail-case caddisflies (Trichoptera: Helicopsychidae) and new records of caddisflies from Chapada Diamantina, Bahia, Brazil. 49 records from Eight new species of Dolichopodinae (Diptera: Dolichopodidae) from northern Iran. 6199 records from SANBI: DNA Banking(1987-2011). 522265 records from RECORD Vascular Plant Data. 4 records from Dinámica poblacional de Mammillaria crucigera y Neobuxbaumia macrocephala en la región de Tehuacán-Cuicatlán. 961 records from Fish monitoring data in Lake Kasumigaura. 41460 records from Herbarium (UNA). 24 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 1368 records from Collection Crustacea ZMG. 78 records from Description of six new species of the genus Ripeacma (Lepidoptera: Oecophoridae) from China, with a checklist of the world species. 1532 records from Biodiversidad acuática del río Amacuzac, Morelos, México. 30985 records from MEXU/Asteraceae. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 93 records from Südwestlich der Parkwiesen. 12 records from Abundance of microplankton from bottle APRIL-2000-K2. 25 records from Benthic foraminifera abundance of Hole 1-4. 18 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-860B. 2000 records from (Table A2) Sea surface temperature reconstruction of DSDP Site 94-607 in the North Atlantic. 7721 records from Chondrichthyans Of Ireland. 8 records from UWYMV Herpetology Collection (Arctos). 37 records from Study on Tychini of Balkan Peninsula (Coleoptera, Staphylinidae, Pselaphinae). 70 records from Tab. A6: Anzahl von M. balthica während der Ansiedlungszeit. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 10 records from Plateurytion roigi sp. nov., a new geophilid centipede (Myriapoda: Chilopoda: Geophilomorpha) from Southern Chile. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 66 records from Foraminifera species abundances from tow TT007_10-MOC20. 177 records from Donauinsel des BN bei Entau. 6 records from Nannofossil abundance of Hole 55-430B. 483 records from Artenvielfalt im Rhein-Neckar-Raum. 11 records from A new species of the catfish genus Akysis (Siluriformes: Akysidae) from southern Borneo.. 127 records from Distribution of planktonic foraminifera of sediment core SH1972_2. 306 records from (Table DR1) Biofacies, percentages of important benthic foraminifera and isotope data at ODP Site 758. 36653 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 32 records from Taxonomic revision of the Malaysian Idiocerinae (Hemiptera: Cicadellidae), with description of new taxa. 1130 records from Ostracoda in sediment core PS51/154-11. 165 records from (Table 3) Ostracode distribution in ODP Hole 122-761C. 1618 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 265 records from CNIN/Mantodea. 176 records from INSECT COLLECTION. 109452 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2007. 40 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D4. 107 records from Planktic foraminifera abundance of Hole 18-180. 99 records from Planktic foraminifera abundance of Hole 94-610E. 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 164 records from Range table from benthic foraminifers in ODP Hole 192-1186A. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 254 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 980 records from Sistemática y biogeografía del género Xenosaurus (Squamata: xenosauridae). 208 records from Programa para la Conservación Integral de Diez Especies de Plantas Prioritarias del BST. 365 records from Bird Specimens of Miyazaki Prefecture Museum of Nature and History. 4554 records from Planktic foraminifera counts (census) of sediment core MD96-2080. 354 records from Relative abundance of planktonic foraminifera in sediment core L-66. 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 2 records from Benthic foraminifera abundance of Hole 42-376. 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 121 records from Dorset Argiope - NBN South West Pilot Project Case Studies. 210 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction > 20µm. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 28 records from Catochini, Strobliellini and Acoenoniini revisited: a taxonomic review of the small tribes of the Micromyinae (Diptera: Cecidomyiidae). 1 records from Description of a new species of Lutosa Walker, 1869 (Orthoptera: Anostostomatidae: Lutosinae) from the Brazilian Atlantic Forest, with biological and behavioral information. 2839 records from Rocky Shore Macroalgae. 29 records from Type specimens and names assigned to Coprophanaeus (Megaphanaeus) d’Olsoufieff, 1924, the largest New World dung beetles (Coleoptera: Scarabaeidae: Phanaeini). 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 227 records from cetacean_strandings_data_bs_as. 13476 records from Regeneración de especies arbóreas del bosque mesófilo en las montañas del norte de Chiapas. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 81 records from Review of the leafhopper tribe Stenometopiini (Hemiptera: Cicadellidae: Deltocephalinae) from China with description of four new species. 252 records from Black grouse leks in the Forest of Clunie, 2002-2011. 201 records from Mammals in MZNA-VERT: project CAS. 1904 records from Escarabajos corprófagos de la cuenca alta y media del río Bita, Vichada (Colombia). 9152 records from Large herbivores in African savannahs, Lake Mburo National Park, Uganda. 23 records from Mains of Kinblethmont Solar Park Amphibian Records 2014. 100 records from Caledonian Conservation Ltd Incidental Records 2014 onwards. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 25713 records from Museu Paraense Emílio Goeldi - Diptera Collection. 60071 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 28 records from Description of two new Calicnemia from Vietnam and central Laos with notes on their congeners in Vietnam (Odonata: Platycnemididae). 33 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 45 records from Plasm bearing foraminifera counts from multinet SO119_MSN1286. 77 records from Total foraminifera counts from M35/1_MSN1075. 228 records from Total foraminifera counts of multinet M36/6_MSN1193. 2 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 4 records from Two new species of Oswaldocruzia (Nematoda, Molineidae) parasitising lizards in Ukraine. 6 records from Two new terrestrial species of Hydraena Kugelann from the island of Bioko, Gulf of Guinea (Coleoptera: Hydraenidae). 145 records from privater Garten. 256 records from BIRDRACE Upupa epöpse. 1294 records from Global Butterfly Information System (GloBIS). 88 records from Total foraminifera counts of multinet SO118_MSN1265. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 26 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 2482 records from V. N. Karazin Kharkiv National University herbarium. 337 records from Abundance of calcareous dinocyst along profile Calais-Escalles. 611 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 46 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 524 records from (Table 2) Benthic foraminiferal composition at University of Texas Marine Science Institute (UTMSI) piston cores at Costa Rican slope sediments. 356 records from Biotope in Rheine - Aktion 350. 50 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/042-2. 87 records from Total foraminifera counts of trap L2_92_B49. 9 records from Microzooplankton abundance and biomass at station TT043_9-1. 1312 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 12 records from Abundance of radiolaria at station LV28-44-1. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 30 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 116 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 120-748. 3458 records from Biodiversidad de Datura (Solanaceae) en México. 2723 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 924 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 2 records from Nothrus palustris. 320 records from Planktic foraminifera assemblage in sediment core GIK11944-1. 3978 records from Colección de Entomopatógenos de México (CNRCB). 2268 records from (Table 1) Distribution of Cretaceous-Tertiary benthic foraminifers in ODP Hole 129-802A. 279 records from Planktic foraminifera abundance of Hole 11-98. 92 records from Range table from planktonic foraminifers in ODP Hole 167-1017B. 2306 records from (Table T4, T5, T6, T7) Percentage of agglutinated and calcareous benthic foraminiferal species in ODP Hole 178-1098C. 19557 records from Collection Thysanoptera SMF. 8 records from A review of the genus Spiropagurus Stimpson, 1858 (Crustacea: Decapoda: Paguridae) from the China seas. 7 records from Synonymy and problematic species of Eiconaxius Spence Bate, 1888, with descriptions of new species (Crustacea: Decapoda: Axiidea: Axiidae). 7938 records from Hymenoptera collection, Natural History Museum, University of Oslo. 389367 records from Effects of vegetation clearing on vascular plants in power line clearings southeast Norway. 3 records from Antarctic Arrow worms. 520 records from SNH Invertebrate Site Condition Monitoring 2015-16: Rum SSSI. 3512 records from (Table 3) Plio-Pleistocene benthic foraminifera of ODP Hole 107-653A. 7966 records from MfN - Phasmid Collection. 679 records from Results of palynological analysis of Hole 302-M0004A. 16476 records from University of Wyoming Dillon Lab Insect Collection. 65 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 1061 records from Antarctic Biodiversity Studies 2006 (Ross Sea, Scott Island, and Balleny Islands) (TAN0602). 31 records from Coleção de Nemertea do Museu Nacional - UFRJ. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 36 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12594-2. 12 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-131BX. 20979 records from CSIC-Real Jardín Botánico-Colección de Hongos Histórica (MA-Funhist). 9371 records from Range table from planktonic foraminifers in ODP Hole 152-918D. 131 records from Range table from benthic foraminifers in ODP Hole 189-1172A. 198 records from Phytoplankton abundance in surface water in January 1996, Pisco, Peru. 63415 records from MMNS Ichthyology Collection. 130 records from Endemic earthworms (Oligochaeta: Lumbricidae) of the Balkan Peninsula: a review. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 144 records from BIRDRACE Punkbirder Helgoland. 24 records from (Table 7) Distribution of Pleistocene to Miocene nannofossils in ODP Hole 108-661A. 27 records from (Table 12) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-666A. 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 65241 records from BeeWalk bumblebee distributions for Great Britain 2008-2016. 9728 records from Birds of Ireland. 9633 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 1271 records from Distribution of planktonic foraminifera of sediment core Core190. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-120BX. 107 records from 1st Austrian Birdrace (Wien). 2402 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 91 records from Benthic foraminifera abundance of Hole 84-569A. 68 records from Range table from benthic foraminifers in ODP Hole 144-873B. 44 records from Flora und Fauna in unserer Kita. 13646 records from Senckenberg - CeDAMar Resource. 549 records from Vertebrates (except birds, INNS and restricted records), Outer Hebrides. 2079 records from (Table 1) Occurrence and frequency of benthic foraminifera in Paleocene samples of DSDP Hole 93-605. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 909 records from Dinámica poblacional de la tortuga de carey (Eretmochelys imbricata) en su área de forraje. Río Lagartos, Yucatán. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 90 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 6563 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 5 records from Colección de Referencia de Reptiles del Museo de Ciencias de la Universidad El Bosque. 12 records from Laccomimus xikrin sp. nov. and new records of other species of Laccomimus Toledo & Michat, 2015 (Coleoptera: Dytiscidae: Laccophilinae) from Brazil. 3710 records from Araneae_Raw1. 9 records from Three new brackish-water thalassocypridine species (Crustacea: Ostracoda: Paracyprididae) from the Ryukyu Islands, southwestern Japan. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 139 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 25 records from A review of subtribe Cymindidina Laporte, 1834 (Coleoptera: Carabidae: Lebiini) in Southwestern Saudi Arabia, with descriptions of two new species. 2029 records from Biodiversidad asociada a mantos de rodolitos y praderas de pastos marinos en Bahía Concepción, BCS. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 7427 records from Weevils of the Tatra Mts.. 2 records from Range extension of the rare braconine genus, Lyricibracon Quicke (Hymenoptera: Braconidae), with the description of a new species from India. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 19206 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 24 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2446-2. 216 records from Monitoreo biológico en la cuenca Dagua - Subcuenca La Guinea ARA - RARE - CVC – Asociación Calidris. 3 records from Mammalia (SMNH-MM). 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 2 records from A new species of Prohatschekia Nunes-Ruivo, 1954 (Siphonostomatoida: Hatschekiidae) from the scorpaenid fish, Scorpaena neglecta Temminck & Schlegel, 1843 (Scorpaeniformes: Scorpaenidae), in Korean waters. 156 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 1826 records from Collection des Mollusques (BOUM). 6 records from Cobitis nalbanti, a new species of spined loach from South Korea, and redescription of Cobitis lutheri (Teleostei: Cobitidae). 49637 records from Monitoring data from the federal state Hesse (Germany). 4 records from Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932. 3 records from Ctenosciara alexanderkoenigi sp. n. (Diptera: Sciaridae), an exotic invader in Germany?. 5 records from Streuobstwiese (Mittelgasse 4). 153 records from Selztal bei Friesenheim. 214 records from Binsenwiesen. 18 records from Landschaftsschutzgebiet Buchhorst2. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 102 records from Plasm bearing foraminifera counts of multinet M12/3_MSN559. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 102 records from Foraminifera species abundances from tow TT011_11-MOC72. 25 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_8-CTD93. 1 records from Nouvelles fourmis d'Afrique.. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 1 records from Erysipelothrix inopinata sp. nov., isolated in the course of sterile filtration of vegetable peptone broth, and description of Erysipelotrichaceae fam. nov.. 1 records from Celaeno spinosa. 87 records from Klütwald. 57 records from Garten in Schmölln. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 347 records from (Table 4) Standing stock values of important species in surface sediments. 181 records from Total foraminifera counts from multinet M31/3_MSN914. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 122 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1359. 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-15-3. 11 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 14 records from Phytoplankton abundance at station Sechin_2003-09-18_1, Casma, Peru. 5 records from Distribution of meiobenthos in sediment core M19_201-2 of the northeastern Atlantic (Table 1). 45 records from Nannofossil abundance of Hole 28-265. 21 records from Meiofauna abundance in sediment core 13077-006. 63 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 42 records from Was singt im Duvenstedter Brook. Wir zählen die Brutvögel im Naturschutzgebiet. 362 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 2088 records from Benthic foraminifera of sediment core MD99-2286. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 206646 records from CPERC Combined Dataset. 57 records from Occurrence of mammalia relicts at site Moladova V. 99 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 117 records from Muskox Abundance. 1 records from Planktic foraminifera abundance of Hole 8-73. 1042 records from Planktic foraminifera abundance of Hole 37-333. 1 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 11 records from Range table from planktonic foraminifers in ODP Hole 178-1096C. 3 records from Range table from planktonic foraminifers in ODP Hole 183-1141A. 96 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 8 records from Pollen and spore abundance of Hole 42-380. 300 records from Gunma Museum of Natural History, Fish Specimen. 578 records from (Figure 2c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3239. 36613 records from Inventaire National du Patrimoine Naturel : Amphibiens et Reptiles de France (Enquête 1). 4 records from Nannofossil abundance of Hole 29-281A. 4 records from Estimated plankton abundance at station PS63/064-6. 8649 records from Fossil (WSHN-FO). 343 records from Collection Cnidaria - ZMB. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 2430 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 2970 records from (Table 2) Distribution of planktonic foraminifera in the latest Oligocene to Holocene section of ODP Hole 149-897C. 154124 records from Arizona State University Lichen Collection. 718 records from Zukünftiges NSG Höftland/Bockholmwik. 96 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 246 records from Benthic foraminifera abundance of Hole 73-524. 494248 records from BLS Mapping Scheme dataset, 1750-2009. 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 764 records from BioGIS - Fish - INPA database. 11268 records from Aphidoidea Collection. 1 records from Leptanillahypodracos sp. n., a new species of the cryptic ant genus Leptanilla (Hymenoptera, Formicidae) from Singapore, with new distribution data and an updated key to Oriental Leptanilla species. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Laguna Las Barrancas (Spitznagel, octubre 1999). 1 records from Damaeus auritus. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 15 records from Fauna of Cladocera and Copepoda from Xinjiang Uyghur Autonomous Region (China). 7683 records from Ickworth Estate species data held by The National Trust. 33 records from Astyanax endy (Characiformes: Characidae), a new fish species from the upper Río Bermejo basin, northwestern Argentina.. 5 records from Aretidris, a new genus of ants (Hymenoptera: Formicidae: Myrmicinae) from the mountains of Luzon Island, Philippines. 12 records from The genus Dromanthomorphus Pic, 1921 (Coleoptera, Cleroidea: Malachiidae) in South-East Asia. 9877 records from Derbyshire Invasive Non-Native Species (INNS) 1900 - 2014. 2 records from Nannofossil abundance of Hole 6-49. 30008 records from Lepidoptera specimen database of Japan. 86 records from Pollen analysis of sediment core GIK16856-2. 76 records from Occurrence of mammalia relicts at site Vindija. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 3 records from Redescription of Lystrocteisa Simon, 1884 (Araneae: Salticidae) from New Caledonia. 50 records from Site condition monitoring of lamprey in the Endrick Water SSSI and SAC, 2012. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-06-4. 4 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 6422 records from Ájtte Collection. 31173 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 22 records from Synonymy of Homalopoltys (Araneae: Araneidae) with the genus Dolichognatha (Araneae: Tetragnathidae) and descriptions of two new species. 5042 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of Environment. 194018 records from Mycology herbarium, Oslo (O). 233 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 3507 records from Flora marina (Clorophyta, Phaeophyta, Rodophyta) y fauna conspicua (Echinodermata, Mollusca, Polychaeta) del Complejo Insular Espíritu Santo-Cerralvo-San José en BCS, México. 1104 records from Mid Ulster Hare Surveys 2012-2015. 47499 records from Sphaeroceridae Collection. 698 records from RISC Non-Native Species Records for Muntjac. 145456 records from NINA insect database. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1952 records from ISM Ichthyology Collection. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 16998 records from Modern foraminifera in the New Zealand EEZ. 1 records from Flora of Suriname, volume VI, part I. 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 114 records from BIRDRACE Di-Bi-Di-Birder. 50 records from Plasm bearing foraminifera counts from M35/1_MSN1047. 193 records from Total foraminifera counts of multinet M21/3_MSN663. 5 records from Rediscovery and redescription of Centrodora damoni (Girault) (Hymenoptera: Aphelinidae) from Australia, an egg parasitoid of Gonipterus spp (Coleoptera: Curculionidae), after nearly a century. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 1165 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 365 records from Colección Herpetológica de la Patagonia. 20416 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 341 records from Inventario y monitoreo de anfibios y mariposas en la Reserva de Calakmul, Campeche. 767 records from Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 1231 records from Registros faunísticos de invertebrados marinos en el SE del Golfo de California. 8 records from Krittenhorster Wald (Ostkilver). 44 records from Total foraminifera counts of multinet M21/4_MSN721. 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 276 records from Planktic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 2 records from Microzooplankton abundance and biomass at station TT050_19-3. 16 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 15 records from Diatom abundance measured on water bottle samples at station PS58/009-2. 129 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 30769 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 103 records from Liste des plantes médicinales utilisées dans la préfecture de Labé et observées sur le terrain.. 144 records from Planktic foraminifera of surface sediments off Portugal and Morocco (Table 4). 83 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 11340 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 1305 records from Myriapoda - SMF. 313162 records from Observational database of Icelandic plants. 2148 records from Eppingen und Umgebung. 127 records from Range table from planktonic foraminifers in ODP Hole 171-1053B. 4244 records from Avifauna de la Reserva de la Biosfera La Sepultura, Chiapas. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 1 records from Oribates mollicomus. 3349 records from Satellite tracking of female olive ridley sea turtles (Lepidochelys olivacea) nesting in the Wessel Islands, Northern Territory, 2005. 142 records from Tejidos de quirópteros de tres localidades del caribe colombiano. 50 records from Lindesnes. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 767 records from BioGIS - Bats - Asaf Tsoar database. 795564 records from Fauna Atlas N.T.. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 1 records from Microzooplankton abundance and biomass at station TT054_24-22. 53 records from On the taxonomy of southern South American species of the wolf spider genus Allocosa (Araneae: Lycosidae: Allocosinae). 3 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 145 records from Phytoplankton abundance at station CD46_0405C#7. 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 18026 records from Herbario micológico de La Universidad de La Laguna, Tenerife: TFC_Mic. 180 records from Donación de la base de datos resultado del diagnóstico de la diversidad de maíces nativos, su agroecosistema y sus parientes silvestres en La Chinantla. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 1295 records from Planktic foraminifera counts of sediment core RC08-49. 921 records from Planktic foraminifera counts of sediment core RC14-37. 3982 records from Plant (GFEI-PL). 9 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-7. 262 records from (Appendix 6) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD95-2041. 314 records from (Appendix 1a) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber in the Holocene section of sediment core GeoTu_SL096. 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 1686 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 1530 records from (Appendix B) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747C. 27828 records from svalbardflora.no. 127 records from Collection Hydrozoa - ZMB. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 29002 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. 9187 records from (Table 14) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-714B. 2483 records from Bacteria collection of National Institute of Public Health, Poland. 193 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-86. 189 records from (Table A.09) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (125-250 µm). 9031 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 296 records from DJH. 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 6 records from Planktic foraminifera abundance of Hole 23-226. 55 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2008. 1139 records from Phytoplankton abundance in surface water in September 1996, Ilo, Peru. 1626 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1119. 631 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 3 records from Report of Platythomisus octomaculatus (C. L. Koch, 1845) and Platythomisus sudeepi Biswas, 1977 from India (Araneae, Thomisidae). 599 records from NHT flora. 92 records from Plasm bearing foraminifera counts of multinet M26/1_MSN843. 39 records from Mineralogy of serpentine muds of ODP Leg 125 holes (Table 1). 2657 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 1154 records from Collection Plecoptera - SMF. 11300 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 1023 records from Spencer Entomological Museum. 141 records from Schulhof und Anlagensee in Nellingen. 269 records from 3. Tag der Artenvielfalt Hockenheim. 10 records from A new species of Neparholaspis (Acari: Parholaspididae) from Russia, with additional information on Neparholaspis evansi Krantz, 1960. 53 records from Occurrence of mammalia relicts at site Roter Berg bei Saalfeld. 15 records from Spiders of the genus Habrocestoides from China (Araneae: Salticidae). 177 records from (Table 11) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-589. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1100C. 159 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 456 records from Range table from benthic foraminifers in ODP Hole 144-873A. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 2346 records from (Fig. 8) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 44-391C in the North Atlantic. 11 records from Observation of birds at station PS14/156 along 49° West. 45 records from Morphological and genetic evolution in eastern populations of the Macrhybopsis aestivalis complex (Cypriniformes: Cyprinidae), with the descriptions of four new species. 7158 records from North East Scotland Mosses and Liverworts (1950-2014). 3621 records from Millenium Seedbank (MSB). 212 records from (Table T4) Planktonic foraminifera abundance of ODP Site 170-1042 sediments. 1387 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 1194 records from Marine Non Native Species records from Natural Resources Wales (NRW) monitoring research and ad-hoc sightings. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 41005 records from MSB Bird Collection (Arctos). 1 records from Diatom abundance of Hole 95-613. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 9513 records from Records of Invasive Non Native Species held on the Cofnod database. 2114 records from Dry Tortugas Reef Visual Census 2010. 2 records from Two new species of the genus Deontolaimus de Man, 1880 (Nematoda: Leptolaimidae) from mangrove ecosystems of Vietnam. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 22 records from Colección Parasitológica del Centro Nacional Patagónico (CNP-PAR). 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 81329 records from natagora-earlybirds. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 34 records from Urolophus kapalensis sp. nov., a new stingaree (Myliobatiformes: Urolophidae) off eastern Australia.. 11 records from Nannofossil abundance of Hole 6-56B. 14 records from Nannofossil abundance of Hole 85-573. 39033 records from SBMNH Vertebrate Zoology. 43 records from Bryconops magoi and Bryconops collettei (Characiformes: Characidae), two new freshwater fish species from Venezuela, with comments on B. caudomaculatus (Gunther).. 86578 records from UPCB - Herbário do Departamento de Botânica. 10567 records from Coleoptera collection of National Museum of Nature and Science. 5432040 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 1 records from Pelops phaeonotus. 1491 records from Formación de las colecciones de referencia de aves y mamíferos de la Reserva de la Biosfera de Sian Ka'an, Quintana Roo, México. 2 records from Parvimyrma gen. nov. belonging to the Solenopsis genus group Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 2 records from A new species of Phyllodytes Wagler, 1830 (Anura, Hylidae) from the Atlantic Forest of southern Bahia, Brazil. 15 records from Discontinuous color variation in the assassin bug species Tiarodes miyamotoi (Hemiptera: Reduviidae: Reduviinae). 5103 records from Elaboración del banco de datos de las colecciones del Museo de Zoología-CIQRO. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 1680 records from Avifauna del Altiplano de San Luis Potosí. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 2985 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 163 records from Tiere und Pflanzen am Pfannenbach. 1 records from Arthropoden aus südostalpinen Höhlen.. 1166 records from Invertebrate data from Selected Grazing Marshes. 17943 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 49 records from Papilionoidea (Insecta: Lepidoptera) type specimens at the Museo de Zoología “ Alfonso L. Herrera ” from Universidad Nacional Autónoma de México. 27 records from Zwickau- Schwanenteich. 30 records from Leben auf einer Sturmfläche. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-19-2. 5 records from Tuttlinger Tag der Artenvielfalt. 1393 records from Lepidoptera from Rancho Grande, Rondônia, Brasil. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 18 records from Planktic foraminifera abundance of Hole 32-310. 3 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 7 records from Additions to the myxobiota of the Åland Islands. 4 records from Arthropoden aus südostalpinen Höhlen.. 190 records from ENBI-Dataset of GART-GloBIS. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 72686 records from NINA Vanndata øvrige arter. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 31 records from Further contribution to the knowledge of Georgian species of the Carabus Linnaeus, 1758 subgenus Neoplectes Reitter, 1885, with description of a new subspecies of C. titarenkoi Zamotajlov & Fominykh, 2014 (Coleoptera: Carabidae: Carabini). 4900 records from Actualización de la colección ictiológica de Ecosur-Chetumal. 20 records from Motzener Tonsee. 18 records from (Table 1) Early Miocene and late Oligocene ostracods in sediment core CRP-2A. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 56647 records from Fish Specimens. 316 records from Planktic foraminifera counts of sediment core V14-101. 615 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part I. 10000 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 190 records from Foraminifera abundance of sediment core MD81-LC07. 3 records from Analyses of the recent components of sediment core PS1215-2. 668 records from Naturschutzgebiet Sistig-Krekeler-Heide. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 120 records from Fiocruz/CYP - Coleção de Yersinia pestis. 692 records from Planktic foraminifera abundance of Hole 40-360. 48387 records from Herbarium of Namur. 94 records from Planktic foraminifera abundance of Hole 80-550. 878 records from Planktic foraminifera abundance of Hole 84-568. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 1 records from Abundance of benthos infauna at station GIK23004-3. 1 records from The Oribatid Family Phthiracaridae I. Introduction and Redescription of Hoplophthiracarus pavidus (Berlese). 72636 records from Insect Collection of Taiwan Forestry Research Institute. 208 records from Thistles damage. 1322 records from Targeting a portion of central European spider diversity for permanent preservation. 7346 records from MfN - Fossil vertebrates III. 28 records from Nannofossil abundance of Hole 26-253. 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 95 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 6663 records from Biodiversidad de los mamíferos en el Estado de Michoacán. 13865 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 973 records from Range table from planktonic foraminifers in ODP Hole 157-954B. 1269 records from Distribution of benthic foraminifers (living) in surface sediments (Table 4). 5 records from New genus and species of Neotropical Colobotheini (Coleoptera, Cerambycidae, Lamiinae). 1 records from A new species of the genus Paratus Simon (Araneae: Liocranidae) from Thailand. 3 records from A new species of Lygistorrhina Skuse (Diptera: Sciaroidea: Lygistorrhinidae) from South Africa. 618 records from Scottish Crossbill National Survey in the UK in 2008. 46 records from Coleção de Brachiopoda do Museu Nacional - UFRJ. 11307 records from Sightings Map of Invasive Plants in Portugal. 356 records from Morphologische Daten von Puffinus creatopus. 11 records from A new Aceria species (Acari: Eriophyidae) from Spain on Pycnocomon rutifolium (Dipsacaceae) and supplementary descriptions of Aceria eucricotes and A. kuko from Lycium spp. (Solanaceae). 25128 records from rmca-albertine-rift-butterflies. 99 records from Düne am Ulvenberg (Darmstadt). 930 records from Benthic foraminifera counts of sediment core PS2644-5. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 147 records from Total foraminifera counts of multinet M36/6_MSN1195. 18 records from Meiofauna abundance in sediment core 13200-012. 577 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 13 records from Description of lithologic section units of IODP Hole 325-M0031A. 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 501 records from Planktic foraminifera assemblage in sediment core SU90-I03. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 73 records from Planktic foraminifera abundance of Hole 2-11. 759 records from Planktic foraminifera abundance of Hole 47-398D. 70 records from Planktic foraminifera abundance of Hole 84-569A. 15 records from Range table from planktonic foraminifers in ODP Hole 169-1036A. 32 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 1512 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 923 records from Collection Graptolithina fossil SMF. 9 records from Re-identification of the material of Neocallichirus maryae Karasawa, 2004 from Ceará, northeastern Brazil, with the first record of N. cacahuate Felder & Manning, 1995 in the southwestern Atlantic. 4 records from The Afrotropical Miomantis caffra Saussure 1871 and M. paykullii Stal 1871: first records of alien mantid species in Portugal and Europe, with an updated checklist of Mantodea in Portugal (Insecta: Mantodea). 1042 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 36 records from Variación genética del manatí (Trichechus manatus), en el sureste de México y monitoreo con radio-transmisores en Quintana Roo. 26464 records from Marie-Victorin Herbarium (MT) - Bryophytes. 50834 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 350140 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Trawl. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 3367 records from Base de datos del Municipio General Heliodoro Castillo, Guerrero (120. Sierra Madre del Sur). 3172 records from ZUEC-COL - Coleção de Coleoptera do Museu de Zoologia da UNICAMP. 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 1 records from A new macropterous species of a rarely collected subfamily (Heteroptera, Tingidae, Vianaidinae). 1374 records from A nest-site survey of Barn swallow at railroad stations in the Kinki District,south-central Japan. 4 records from A new species of the genus Paramesotriton (Caudata: Salamandridae) from Fujian, southeastern China. 3 records from Two new species of Jogocerus Viraktamath (Hemiptera: Cicadellidae: Idiocerinae) from China. 61 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 244 records from WildesMoor bei Schwabstedt. 144 records from Total foraminifera counts of multinet M21/2_MSN640. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 1 records from Microplankton counts and carbon biomass at station TT007_15-CTD160. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 3 records from Nannofossil abundance of Hole 51-417D. 1547 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM. 11981 records from SMNK Mantid Collection. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 753 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 10 records from Saying goodbye to monotypy in the poorly known genus Austrophyto Lopes, 1989 (Diptera: Sarcophagidae): new diagnosis and description of two new species. 166 records from Simpson´s diversity of Coleoptera and Heteroptera. 554 records from SNH Invertebrate Site Condition Monitoring 2013/14: Abernethy Forest SSSI. 13 records from Tag der Artenvielfalt am Bruckenwasen. 161 records from BIRDRACE Nord-Seh-Team. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 2 records from An extraordinary new genus and species of spider wasps (Insecta: Hymenoptera: Pompilidae) from Southeast Asia. 82 records from Foraminifera species abundances from tow TT011_5-MOC63. 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 26 records from Ostracoda abundance of Hole 13-132. 82 records from Fiocruz/CLEP - Coleção de Leptospira. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 133 records from Catalogue of type specimens of fungi and lichens deposited in the Herbarium of the University of Granada (Spain). 60000 records from Birds (NSMK-BI). 25372 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 8 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 16 records from Dinoflagellate cysts of surface sediments. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD11. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-12-1. 68 records from Macrofauna abundance in surface sediment sampled during cruise DI229. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 221 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 56051 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 91 records from CNIN/Tipos Homoptera. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 105 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 6264 records from (Table 2) Planktic foraminiferal abundance in Eocene to Oligocene sediments of ODP Hole 177-1090B on the Agulhas Ridge, South Atlantic. 55 records from Three new species of Ametadoria Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, Costa Rica. 264743 records from ArtenFinder. 569 records from (Appendix D) Benthic foraminifera extinction group species in DSDP Hole 94-608. 6814 records from Sammmlung Ule Brasilien Herbarium Hamburgense HBG. 1078 records from Fishes of the Congo River 2010 Expedition. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 315446 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 1379 records from Organic-walled dinoflagellate cyst counts of sediment core GeoB9503-5. 5 records from Colección de Referencia de Platelmintos del Museo de Ciencias de la Universidad El Bosque. 8 records from Occurrence of mammalia relicts at site Grotte du Prince. 27264 records from Formidabel; Belgian Ants Database. 1863 records from Cowan Tetrapod Collection - Herpetology. 609 records from Countryside Council for Wales - Bat Roosts Database- South Wales. 852 records from flower availability 2008 Hainich. 9948 records from Bees of Canada / Gschwendtner property collection. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 8 records from Abundance of radiolaria at station LV28-29-1. 2 records from Nannofossil abundance of Hole 74-526. 66 records from Range table from ostracoda in ODP Hole 151-910D. 124 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 535 records from Benthic foraminifera abundance of Hole 73-522. 27 records from Benthic foraminifera abundance of Hole 34-320A. 302 records from Range table from benthic foraminifers in ODP Hole 144-874B. 75 records from Range table from nannofossils in ODP Hole 199-1220A. 585 records from (Tab. 4) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 11-105, Bahama Lower Continental Rise Hills. 31 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 1 records from Nouvelles fourmis de l'Imerina oriental (Moramanga etc.).. 143 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 161 records from (Table 3) Palynomorph concentrations for ODP Site 105-645. 988 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 156 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 190 records from Colección Paleontológica Invertebrados e Icnologia - CONICET- Argentina. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 143763 records from University of British Columbia Herbarium (UBC) - Algae Collection. 1432 records from Quaternary benthic foraminifera abundance of Hole 95-612. 940 records from Benthic foraminifera abundance of Hole 84-570, Part 2. 226 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 227 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 1051 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 32 records from City of Edinburgh Natural Heritage Service - Hermitage Wildflower Meadow. 1 records from First record of the subgenus Duolandrevus (Duolandrevus) (Orthoptera: Gryllidae: Landrevinae) from China, with description of a new species. 7 records from A new Eastern Central Atlantic skate Raja parva sp. nov. (Rajoidei: Rajidae) belonging to the Raja miraletus species complex. 208 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 44501 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 1251 records from Visual Plants (144.41.33.158) - Herbarium specimen from "EA", Kenya. 1346 records from Percentages of planktonic foraminifera species in sediment core V25-59. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 65 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 7 records from Three new species of phytoseiid mites (Acari: Phytoseiidae) from Bahia State, Brazil. 92 records from Siliceous microfossil occurrence, Site 177-1094. 610 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 45 records from Parcela Permanente en el Pantano Martos. 281250 records from Quadrige. 2 records from A new karst dwelling species of the Gekko japonicus group (Squamata: Gekkonidae) from central Laos. 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 187 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 75 records from (Table S2b) Nannofossil species richness in the Wilson Lake section. 4636 records from Las monocotiledóneas mexicanas, una sinopsis florística. Parte II. 92 records from Flora vascular de los manglares de Marismas Nacionales, estado de Nayarit. 1030627 records from Phanerogamic Botanical Collections (S). 270 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 4 records from A new genus of Silvaninae (Coleoptera: Silvanidae) with two new species from the Malay Peninsula. 2 records from A second species, and first Central American record, of the phorid fly genus Lenkoa Borgmeier (Diptera: Phoridae). 3497 records from SEWBReC Reptiles (South East Wales). 27 records from New records of Sylvicola (Diptera: Anisopodidae) from Romania. 2653 records from Florida Keys Reef Visual Census 2005. 10 records from Revision of the genus Angaracris Bey-Bienko, 1930 (Orthoptera: Acrididae, Oedipodinae) with notes on the tribe Bryodemini. 54 records from Wiese am Unterbecken. 2 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 84 records from BIRDRACE Vogelscheuchen. 72 records from Plasm bearing foraminifera counts of multinet M21/1_MSN603. 90 records from Total foraminifera counts of multinet PO231/3_MSN1332. 33 records from Foraminifera species abundances from tow TT007_2-MOC4. 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 706 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 4 records from Microzooplankton abundance and biomass at station TT054_24-21. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_5-CTD51. 42619 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 6 records from Ökosysteme rund um Wedel. 16 records from Nannofossil abundance of Hole 47-398B. 14 records from A new subterranean Iberian Cephennium with unusually modified metatrochanters (Coleoptera, Staphylinidae, Scydmaeninae). 229426 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 387894 records from University of Florida Vertebrate Paleontology. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 2 records from A new species of the genus Asthenara Förster, 1869 (Hymenoptera, Ichneumonidae) from Mexico with identification key. 23 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 12 records from Distribution of meiobenthos in sediment core M23_134 of the northeastern Atlantic (Table 1). 36845 records from MfN - Fossil invertebrates Ia. 29 records from Composition of the fine silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 3062 records from Algae collection. 104 records from Ross Sea Pycnogonids. 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE258. 7468 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 1263 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 102 records from Ostracod abundance in sediment core Lz1120. 855 records from (Table T7) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones Palpha-P3b. 4054 records from Locations of seals in Patagonian Large Marine Ecosystem (OBIS South America, AR-OBIS, Sub-node). 464 records from Lepidoptera collection, NTNU University Museum. 718 records from HSU Vertebrate Museum Amphibian Collection. 1965 records from Global caridean shrimp fauna. 61 records from The water mite family Aturidae Thor (Acari: Hydrachnidia) from Ghana, with the description of twelve new species. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 6 records from Microzooplankton abundance and biomass at station NBP97-08-04-5. 2 records from Two new Australian fungus-feeding thrips in two new Plectrothripini genera (Thysanoptera, Phlaeothripinae). 2 records from Smear slide analysis of sediment core GeoB7427-2. 71 records from Range table from nannofossils in ODP Hole 199-1215A. 195 records from Phytoplankton abundance in surface water in May 1997, Callao, Peru. 103 records from Catalogue of snout mites (Acariformes: Bdellidae) of the world. 3 records from Taxonomic note on Abax contractus (Heer, 1841) and description of A. parallelepipedus ligurinus n. subsp. (Coleoptera, Carabidae, Pterostichini). 13 records from Siphonoecetini Just, 1983 (Crustacea, Amphipoda, Ischyroceridae) 11: Cephaloecetes schioettei sp. nov. from The Philippines. 1474 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 1 records from Emesopsis infenestra Tatarnic, Wall & Cassis, 2011 (Heteroptera: Reduviidae), genus and species new to New Zealand. 17 records from Description of Brachymeria philornisae sp. n. (Hymenoptera: Chalcididae), a parasitoid of the bird parasite Philornis trinitensis (Diptera: Muscidae) in Tobago, with a review of the sibling species. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 527 records from Inventaire floristique de Beza Mahafaly. 8 records from Generic reclassification of species formerly included in Rhantus Dejean (Coleoptera, Dytiscidae, Colymbetinae). 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 71 records from (Table 3d) Distribution of planktonic foraminiferal tests in sediments from Core NKA-4T. 26375 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 577 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 106 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Dana Uster. 366 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 131 records from Artenvielfalt auf dem Schulgelände. 741 records from Planktic foraminifera abundance of Hole 20-200. 3651 records from Planktic foraminifera abundance of Hole 72-516F. 93712 records from Herbarium of Umeå University (UME). 2190 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 2632 records from Anglesey Abbey wildlife species data held by The National Trust.. 47289 records from Naturalis Biodiversity Center (NL) - Porifera. 30 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 2 records from A new Schistura from the Salween basin in western Yunnan (Teleostei: Nemacheilidae). 3034 records from Caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 21 records from Hungarosoma bokori Verhoeff, 1928 (Diplopoda: Chordeumatida): new insights into its taxonomy, systematics, molecular genetics, biogeography and ecology. 15016 records from iziko South African Museum - Fish Collection (AfrOBIS). 588 records from Distribution ashore and breeding places of southern elephant seals. 34506 records from Herbarium de Geo. B. Hinton, México. 3015 records from Bird specimens in Gifu Prefectural Museum. 535 records from Percentages of planktonic foraminifera species in sediment core V30-41. 342 records from Distribution of planktonic foraminifera in sediment core R657 east of New zealand. 155 records from Bergbaufolgelandschaft am Muldestausee. 8 records from Occurrence of mammalia relicts at site Wretton. 994 records from (Table 6) Quaternary planktonic foraminifers at DSDP Site 65-483. 465 records from Range table from planktonic foraminifers in ODP Hole 159-959A. 727 records from Range table from benthic foraminifers in ODP Hole 161-975B. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 14 records from Collection Pantopoda SMF. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 1 records from Arthropoden aus südostalpinen Höhlen.. 5147 records from Códigos de barras de la vida en peces y zooplancton de México. 6 records from Two new species of Melanorivulus (Cyprinodontiformes: Cynolebiidae) from Rio Verde drainage, Upper Rio Paraná basin, Brazil. 14 records from Description of three new troglobiontic species of Cybaeodes (Araneae, Liocranidae) endemic to the Iberian Peninsula. 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 1833 records from DSMZ Fungi. 3034 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 21 records from Two new species of Bothriurus Peters, 1861 (Scorpiones, Bothriuridae) from Northeastern Brazil. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 2387 records from The French Collection of Medicago truncatula. 82 records from On the spider (Aranei) fauna of the Pechoro - Ilychskiy Reserve (North Urals), with the description of a new Agroeca species (Liocranidae). 2097 records from Base de datos de la familia Cactaceae de la Península de Baja California, México. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 1 records from Nothrus scaliger. 11 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_236-1. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_11-CTD137. 5 records from Phytoplankton abundance at station Rigel_5_2005-07 in July 2005, Chipana, Chile. 1000 records from Diplopoda (JJHA-DI). 149 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 438 records from (Table 4) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-709A. 2241402 records from Biologiezentrum Linz. 294 records from Naturgarten Langenholtensen. 42 records from Foraminifera abundance of Hole 24-236. 960 records from (Table 11) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-591. 156 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 139 records from Siliceous microfossil occurrence, Site 177-1093. 55 records from Review of the Priocnemis hyalinata species-group (Hymenoptera: Pompilidae), with description of a new species from China. 11 records from Etmopterus burgessi sp. nov., a new species of lanternshark (Squaliformes: Etmopteridae) from Taiwan.. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 6797 records from UPRM Invertebrate Collection. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 15616 records from Swift Inventory of Nest Sites in the UK, 2009-2014. 13968 records from NYSM Birds. 1447 records from Odonata of the Congo River 2010 expedition. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 241 records from BIRDRACE RennVögel Münsterland. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 112 records from BIRDRACE Gütersloher Gimpel. 67 records from Tongrube bei Hettstedt. 65535 records from OAC-BIO Herbarium. 70 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1387. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_1-CTD8. 1000 records from Plant (KOBG_PL). 148 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE293. 300 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part II. 2022 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 401 records from Noble Chafer: Post-BAP records from 1998 onwards. 9123 records from Flora of Słowiński National Park, Poland. 2 records from Discovery of a new millipede species in northern Vietnam, and the proposal of a new genus, Parariukiaria (Diplopoda, Polydesmida, Xystodesmidae). 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 7950 records from European riparian ground beetles. 2877 records from Flea collection of Slovenian Museum of Natural History (Slovenia only). 104 records from Total foraminifera counts of multinet M21/6_MSN778. 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 3 records from Sarcodine counts and carbon biomass at station TT011_2-CTD21. 5112 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 17 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/011-3. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 8200 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 156 records from (4) Assemblages of planktic foraminifera and Sea Surface Temperature (SST) reconstructed from the Modern Analogue Technique in sediment core MD02-2488 during the Last Interglacial. 7684 records from Seed bank grassland. 44 records from Planktic foraminifera abundance of Hole 19-188. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 5 records from The genus Eremiothrips (Thysanoptera: Thripidae) from China, with one new species. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 57 records from Schulgarten Janusz-Korczak-Realschule. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 48 records from Diatom assamblage in samples from sediment trap OG5. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 777 records from Planktic foraminifera counts of sediment core RC17-108. 45 records from Wasser-Lernort Nettemündung. 1 records from Antarctic Marine Amoebae. 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 73544 records from Marsh Monitoring Program - Birds. 11054 records from Colección de Sifonápteros del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 52 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 24 records from Occurrence of mammalia relicts at site Overmere. 7 records from Radiolaria assemblage in sediment core GIK23424-3. 2083 records from Planktic foraminifera abundance of Hole 72-517. 115 records from Range table from planktonic foraminifers in ODP Hole 155-931C. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 57 records from Heidesee / Halle. 60 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Steffen Matezki. 11370 records from Distribution of planktic foraminifers of core V22-174. 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 7 records from Boraginaceae (Cynoglossum cherangauiense). 13702 records from Fundación Miguel Lillo - Colección Ornitológica. 340 records from Occurrence of mammalia relicts at site Brillenhöhle. 15 records from Herdengelhoehle taxa and datings. 520 records from Planktic foraminifera abundance of Hole 39-357. 7 records from Range table from planktonic foraminifers in ODP Hole 192-1185B. 157 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 19 records from Dinoflagellate abundance of Hole 81-553A. 2629 records from Data on medicinal plants of Benin. 4 records from Two new troglobiotic palpigrades (Palpigradi: Eukoeneniidae) from Brazil. 41 records from Revision and phylogeny of the Caribbean weevil genus Apotomoderes Dejean, 1834 (Coleoptera, Curculionidae, Entiminae). 175 records from Revisión periódica de Agave victoriae-reginae en el apéndice II de la CITES. 3535 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 2 records from Porifera ZMK. 96 records from Birdrace-federleser-Herford. 147 records from NABU-Auerochsenweide. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 3343 records from SMNS Palaeontological collection - Fossil aquatic vertebrates. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from On the Chilopoda from Turkey. 681 records from (Appendix) Planktonic foraminiferal abundances in ODP Hole 130-805C. 63 records from Morphology-based phylogeny of the suckermouth armored catfishes, with emphasis on the Neoplecostominae (Teleostei: Siluriformes: Loricariidae). 16493 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleovertebrates National Collection (MACNPv). 7056 records from EAN - Herbário Jaime Coelho de Moraes. 1 records from Taxonomic description and 3 D modelling of a new species of myzostomid (Annelida, Myzostomida) associated with black corals from Madagascar. 2 records from Mealybugs (Hemiptera: Coccomorpha: Pseudococcidae) with oral rim ducts; description of a new genus and species from Turkey, and discussion of their higher classification within the Pseudococcidae. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 14590 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 157 records from Contribution to the knowledge of Chinese Phasmatodea III: Catalogue of the phasmids of Hainan Island, China, with descriptions of one new genus, one new species and two new subspecies and proposals of three new combinations. 21572 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 490 records from flower availability 2007 Schwäbische Alb. 5341 records from CHAS Mammalogy Collection (Arctos). 69546 records from Fundación Miguel Lillo - Colección Entomológica. 102 records from Benthic foraminifera abundance of Hole 42-372. 1 records from Microfossil abundance of Hole 42-378. 1312 records from (Table 3) Distribution of benthic foraminifers in the > 63 µm fraction in surface sediments from the central Arctic Ocean. 1 records from Abundance of benthos infauna at station GIK23062-2. 209 records from pflanzendiversitaet_2008_sch_zweiter_durchgang. 2 records from Nebria (Patrobonebria) incognita n. sp. and Nebria (P.) hiekeiana n. sp., two new species from the Western Himalaya, with remarks on Nebria (P.) desgodinsi (Coleoptera, Carabidae, Nebriinae). 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 3 records from A new species of the genus Leptobrachium (Anura: Megophryidae) from the Gaoligongshan Mountain Range, China. 1 records from On the genus Sunius Curtis, 1829 of Turkey. IV. A new micropterous species from southwestern Anatolia and additional records (Coleoptera: Staphylinidae: Paederinae). 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 100 records from Birdrace-The_Ringers-Friesland. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 50703 records from Seasearch Marine Surveys in Ireland. 498 records from Dinoflagellate abundance of Hole 94-611C. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 495 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 50 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 112 records from Total foraminifera counts of multinet M11/1_MSN526. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 1308 records from Dinoflagellate cysts counts of sediment core MD95-2010. 85 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 212 records from Nanoplankton abundance at station GeoB2017-1. 49 records from Three new species and one new subspecies of Deserticossus Yakovlev, 2006 (Lepidoptera: Cossidae) from Kazakhstan, Kyrgyzstan and Russia, with world catalogue of the genus. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/091-4. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/546-2. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 116 records from (Table 17) Distribution of planktonic foraminifers in ODP Hole 108-668B. 1680 records from Estudio comparativo del zooplancton en dos regiones de México. 5429 records from Ibaraki Nature Museum, Algae collection. 355 records from (Table A3) Semi-quantitative frequency of Globorotalia menardii in core SO164-17-2. 23146 records from BC Coastal Waterbird Survey. 35693 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2002) (AfrOBIS). 8684 records from Individual Sightings. 28934 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 16016 records from Field Survey. 77 records from Total foraminifera counts of multinet PO231/3_MSN1330. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 40 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2215-1. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 1634 records from ZFMK DORSA. 180 records from Range table from ostracoda in ODP Hole 144-871A. 349 records from Planktic foraminifera counts of sediment core V20-170. 6659 records from Anfibios y Reptiles del Estado de Tamaulipas, México (UANL). 2050 records from Birds (ENHM-BI). 1537 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 108-657A. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 777 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 72615 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 70704 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1988) (AfrOBIS). 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 94474 records from TNHC Herpetology Collection. 66 records from Visual Plants (144.41.33.158) - Private collection of Thorsten Kroemer. 655 records from Planktic foraminifera assemblage in sediment core GIK17049-6. 3224 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 26403 records from EWT: African Crane Conservation Programme Sightings. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 21 records from Consolidated Checklist of Hard Corals of the Genus Acropora Oken, 1815 (Scleractinia: Acroporidae) in North Borneo, East Malaysia. 1843 records from (Table 3) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 2166 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 736 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 6 records from Gobiesox lanceolatus, a new species of clingfish (Teleostei: Gobiesocidae) from Los Frailes submarine canyon, Gulf of California, Mexico. 222 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 25 records from A new Gymnotus (Teleostei: Gymnotiformes: Gymnotidae) from the Pantanal Matogrossense of Brazil and adjacent drainages: continued documentation of a cryptic fauna.. 5262 records from Spider Mites Collection of Jean Gutierrez. 1968 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Pinus sylvestris pioneer forest. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae. 14473 records from Entomology at ZMUC, Natural History Musem of Denmark. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 3057 records from Florida Keys Reef Visual Census 2010. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 172 records from Foraminifera abundance of Hole 59-448A. 944 records from Range table from planktonic foraminifers in ODP Hole 192-1183A. 72 records from Range table from benthic foraminifers in ODP Hole 198-1213A. 13733 records from Collection Bryozoa SMF. 1147 records from Herpetofauna de la región El Huizache, San Luis Potosí. 14533 records from MVZ Egg and Nest Collection (Arctos). 486 records from UAM Herpetology Collection (Arctos). 21 records from Unveiling of a cryptic Dicranomyia (Idiopyga) from northern Finland using integrative approach (Diptera, Limoniidae). 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 228 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 15 records from Fiocruz/CENT - Coleção de Enterobactérias. 31190 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 1506 records from Computarización de la Colección de Referencia para Zoología, Arqueozoología y Paleontología del Museo de Historia Natural de la Universidad Autónoma de Baja California Sur. 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 1581 records from Collection of Occurrence data on mammal species during wildlife census in W Biosphere Reserve in 2013 and 2015. Data mobilized in the framework of the BID-AF2015-0030-SMA project of Isidore Amahowe. 5 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 1998 records from Aves de la cuenca media del río Bogotá. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 2 records from Orthotrichum dentatum T. Kiebacher & Lüth sp. nov. (Orthotrichaceae). 1835 records from ARKO Overvåking kalklindeskog. 6 records from Coleção de Tardigrada do Museu Nacional - UFRJ. 2808 records from Dipterists Forum - Field Weeks 2000 & 2001 (Cornwall & Devon). 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 6717 records from LSUMZ Mammal Tissues. 8 records from Phytoplankton abundance at station Rigel_6_2005-03 in March 2005, Chipana, Chile. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 596 records from Planktic foraminifera counts of sediment core A15-558. 2792 records from Birds (UWEP-BI). 97 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 115 records from (Table 2a) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Canary upwelling. 82756 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1992) (AfrOBIS). 1101 records from Relative abundance of ostracods in sediment core Co1202. 173 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 1 records from A new generic name, Semigothograptus, for Gothograptus? meganassa Rickards & Palmer, 2002, from the Silurian post- lundgreni Biozone recovery phase, and comparative morphology of retiolitids from the lowermost upper Homerian (upper Wenlock). 344 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 77 records from ZUEC-AST - Coleção de Asteroidea do Museu de Zoologia da UNICAMP. 73 records from AMF colonization in Plantago. 1 records from Nothrus pollinosus. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 163 records from Total foraminifera counts from multinet SO119_MSN1285. 169 records from Planktic foraminifera counts at CTD station PS55/051. 1409 records from Planktic foraminifera counts of sediment core AB000280. 753 records from Planktic foraminifera counts of sediment core V28-127. 3161 records from Distribution of foraminifera of sediment core ENAM93-21. 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 1 records from Dinoflagellate abundance of Hole 19-183. 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 681 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 2 records from High diversity of Caligus species (Copepoda: Siphonostomatoida: Caligidae) in Taiwanese waters. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 6086 records from Computarización de las colectas del estado de Morelos depositadas en el Herbario HUMO de la Universidad Autónoma del Estado de Morelos. 778 records from City of Edinburgh Natural Heritage Service - Historical Records. 255 records from GENT Lactarius Deliciosi. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 568 records from Expedición Providencia I - INVEMAR. 20992 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 1733 records from Birds collection of Abiko City Museum of Birds. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 76 records from Faunal assemblage of sediment core GS7603-10. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 52 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1382. 11 records from Content of coarse fraction and G. menardii in sediment corev V25-39. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 35 records from Nannofossil abundance of Hole 78-543. 9 records from Nannofossil abundance of Hole 1-2. 6 records from Nannofossil abundance of Hole 6-49. 7 records from Nannofossil abundance of Hole 38-336. 36 records from Nannofossil abundance of Hole 14-141. 24121 records from Endemic plants of the Congo basin. 1495 records from Museu Paraense Emílio Goeldi - Mollusca Collection. 83 records from Species of the Genus Salda F. (Heteroptera, Saldidae) of the Fauna of Russia and Adjacent Territories. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 85 records from Black grouse lek survey in Ross-shire. 91 records from BIRDRACE SchrägeVögel. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 171 records from Total foraminifera counts of multinet M42/3_MSN1370. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 32 records from Microzooplankton abundance measured on water bottle samples at station PS65/593-3. 1088 records from (Appendix 2-1) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 7-62A in the western Pacific Ocean. 135 records from (Table A.08) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (80-150 µm). 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/580-2. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 22459 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 2184 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 16489 records from AIMS - GBR Nearshore Coral Diversity (OBIS Australia). 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 591 records from Planktic foraminifera counts of sediment core V16-25. 2000 records from Shellfish (ASJK_MS). 2073 records from Bryophyte collection of Jyväskylä University Museum. 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 1134 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 363 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 168 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2009. 3666 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 15506 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 5205 records from Botanical Garden Collection. 30501 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 6627 records from ATCC Fungi Collection Catalog. 424 records from Bulk components and planktonic foraminifera of sediment core GeoB3375-1. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 98 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 1298 records from Planktic foraminifera abundance of Hole 23-219. 371 records from Planktic foraminifera abundance of Hole 63-470. 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 274 records from Herpetological Collection at the Wildlife Institute of India Vertebrate Museum. 19 records from Microplankton data off Mejillones, 2006, Chile. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 8276 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 43 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM5. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Sturnidae. 44 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America Part I. Genus Scatopsciara Edwards, 1927. 3062 records from Mamíferos silvestres de la cuenca del río Mezquital-San Pedro, Durango-Nayarit. 21 records from On the Lathrobium fauna of the Luoxiao Mountains, Central China. 66591 records from Tasmanian Museum and Art Gallery provider for OZCAM. 10 records from Maculabatis ambigua sp. nov., a new whipray (Myliobatiformes: Dasyatidae) from the Western Indian Ocean. 70 records from New species of Ameletus Eaton, 1885 from the Russian Far East with notes on Ameletus camtschaticus Ulmer 1927 (Ephemeroptera: Ameletidae). 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 95 records from Vielfalt verschiedener Wiesen. 504 records from Schatzinsel Wangerooge. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 1380 records from Range table from benthic foraminifers in ODP Hole 189-1168A. 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 9128 records from Verified Marine records from Indicia-based surveys. 15 records from Pogonophora collection of National Museum of Nature and Science. 2 records from Two interesting new ground spiders (Araneae) from the Canary Islands and Greece. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 85 records from Birdrace-Die_Paradiesvögel-Herford. 248 records from Schulgarten der Volksschule. 33 records from Schüler erforschen die Helme-Aue. 100 records from Total foraminifera counts of multinet M12/3_MSN536. 73 records from Mycophagous gall midges (Diptera, Cecidomyiidae: Lestremiinae, Micromyinae, Winnertziinae, Porricondylinae): first records in Sweden and descriptions of closely related new species from elsewhere. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 1301 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 8 records from Nannofossil abundance of Hole 49-409. 260 records from Range table from ostracoda in ODP Hole 144-873B. 28 records from (Table 4) Range chart of calcareous nannofossils from Ross Sea sediment cores. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 3 records from A new genus and species of Laelapidae (Acari: Mesostigmata) from Iran. 221 records from (Table 1) Abundance of planktonic foraminifera in ODP Hole 113-689B, large size fraction. 132 records from Cretaceous ostracods of DSDP Hole 10-95 (Figure 2). 1607 records from Range table from benthic foraminifers in ODP Hole 162-986D. 36 records from Range table from planktonic foraminifers in ODP Hole 144-877A. 84 records from Benthic foraminifera abundance of Hole 84-566C. 38 records from Microfossil abundance of Hole 21-206C. 7457 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 270656 records from KU Museum of Invertebrate Paleontology. 359044 records from Insect (KNAM-IN). 29 records from Description of two new species of Hetereleotris (Gobiidae) from the south Pacific, with a revised key to species and synonymization of the genus Pascua with Hetereleotris.. 6665 records from Shieldbug & allied species records, from iRecord. 1794 records from Herbarium BSG Lichenes. 9137 records from CRI - Herbário Pe. Dr. Raulino Reitz. 815439 records from Royal Botanic Garden Edinburgh Herbarium (E). 1199926 records from Waarnemingen.be - Plant occurrences in Flanders and the Brussels Capital Region, Belgium. 118315 records from Mammalogy Collection - Royal Ontario Museum. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 10 records from New species of Zenoria Mulsant (Coleoptera: Coccinellidae) from Brazil and Peru. 39 records from Red list project inventory, fungi. 40 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 41308 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 10075 records from Nematoda of Costa Rica (INBio). 957 records from Computarización de la Colección nacional del phylum Porifera Gerardo Green. 55317 records from Local Wildlife Site Surveys Berkshire. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 18 records from Nivalios gen. nov. (Hemiptera: Fulgoromorpha: Flatidae), first record of the tribe Nephesini from China. 27 records from synthese_Protistdiversity_KG. 16 records from Hazel Dormouse in Ireland. 6 records from Mammalia (JNHM-MM). 43 records from Schulgelände Thurmair-Gymnasium. 300 records from Estudio monográfico de los gasteromicetos del noroeste de Baja California, México. Provincia Californiana. 3 records from Blankenfelder See. 129 records from Nannofossil abundance of Hole 29-284. 48 records from SNH Invertebrate Site Condition Monitoring 2015: Tweedwood - Gateheugh SSSI. 1301 records from Collection Hymenoptera SMF. 68081 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 30000 records from Freshwater Fish Specimens of Lake Biwa Museum. 8523 records from Distribution of planktic foraminifers of core RC24-16. 336 records from Site Condition Monitoring Records from surveys of lamprey species in five river SACs in Scotland. 15 records from Occurrence of mammalia relicts at site Dendermonde. 437 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1421 records from Weevils of Poland. 1584 records from Registro de vertebrados durante el fototrampeo del convenio 027 - 2014 CVC - Panthera. 491 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 2 records from A redescription of Lophostica mauriciana Simon, 1902 (Araneae: Salticidae). 98952 records from CAS Ornithology (ORN). 1 records from Zetes morticinus. 65 records from BIRDRACE Federal Birds of Investigation FBI. 10 records from A new species of Gastrozona Bezzi (Diptera: Tephritidae: Dacinae: Gastrozonini) with an updated key to species from India. 2 records from Range table from nannofossils in ODP Hole 198-1207A. 22 records from Steinbruch Mainz-Weisenau, 4.Jahr. 26 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 30000 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 2 y 3. 2184 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 2730 records from (Table 10) Distribution of planktonic foraminifera in the middle to late Miocene section of ODP Hole 149-900A. 379 records from Relative abundance of planktonic foraminifera in sediment core MK-325. 1458 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 1312 records from GEO-Hauptveranstaltung (Insel Vilm). 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 186 records from Planktic foraminifera abundance of Hole 94-610. 5944 records from (Figure 6) Distribution of benthic foraminifers in middle-upper and Quaternary in DSDP Site 71-512. 90 records from Collection Ctenophora SMF. 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 318 records from Geometry of coccolith Coccolithus pelagicus in ODP Hole 104-643A. 12 records from Nannofossil abundance of Hole 20-200. 16 records from Nannofossil abundance of Hole 9-77B. 945 records from (Table 7) Distribution of planktonic foraminifers in ODP Hole 108-660A. 3726 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 580 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 7 records from Analyses of the recent components of sediment core PS1219-1. 4 records from A new species of Auriculostoma (Trematoda: Allocreadiidae) from the intestine of Brycon guatemalensis (Characiformes: Bryconidae) from the Usumacinta River Basin, Mexico, based on morphology and 28 S rDNA sequences, with a key to species of the genus. 50 records from Planktic foraminifera abundance of Hole 60-457. 2 records from Range table from planktonic foraminifers in ODP Hole 144-874A. 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 63646 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 15 records from Description of a new species of Neoromicia (Chiroptera: Vespertilionidae) from southern Africa: A name for “ N. cf. melckorum ”. 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 22 records from A new species of Buenia (Teleostei: Gobiidae) from the western Mediterranean Sea, with the description of this genus. 8594 records from ColRest_Raw1. 4774 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 85439 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1987) (AfrOBIS). 21348 records from Phytopathogenic Fungi Observed by Hans and Hanna Doppelbaur. 495 records from Life Science National Tsing Hua University. 994 records from Distribution of planktic foraminifera in sediment core GIK23074-1. 239 records from Naturerlebnisraum Koppelsberg. 1 records from Nothrus theleproctus. 3 records from ALERT Non-Native Species Records for Signal Crayfish. 1093 records from Systematic studies on Pseudomyrmex acacia-ants (Hymenoptera: Formicidae: Pseudomyrmecinae). 7848 records from Lichen specimen database of Faurie collection. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 32 records from Ice Zooplankton Beaufort Sea. 1905058 records from Museum of Comparative Zoology, Harvard University. 22 records from Review of amphipods of the Melita group (Amphipoda: Melitidae) from the coastal waters of Sakhalin Island (Far East of Russia). III. Genera Abludomelita Karaman, 1981 and Melita Leach, 1814. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 11 records from Phytoplankton abundance at station Rigel_4_2005-03 in March 2005, Chipana, Chile. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 5 records from Schulwald Regionale Schule Sprendlingen. 3 records from Nannofossil abundance of Hole 22-212. 1129 records from Mollusca Collection of Saitama Museum of Natural History. 775 records from Insect (GNHM-IN). 17 records from A review of the genus Pareuchiloglanis (Sisoridae) from the Lancangjiang (upper Mekong River) with descriptions of two new species from Yunnan, China.. 2 records from Eine neue Art der Gattung Suctobelba Paoli (Suctobelba vera n. sp.) aus Deutschland (Acarina: Oribatei). 8063 records from (Appendix B1) Relative abundances of middle Eocene-late Oligocene calcareous nannofossils in ODP Hole 120-748B. 2365 records from Sutton Hoo species data held by The National Trust. 796 records from (Data S1) Palynology of IODP Hole 318-U1356A. 730 records from MATRIX project, Budongo fragments birds. 5 records from Three new species of Mesonemoura (Plecoptera: Nemouridae) from China. 27847 records from Dataset of Passerine bird communities in a mediterranean high mountain (Sierra Nevada, Spain). 471508 records from SER Species-based Surveys. 350 records from Speothos Venaticus por Guillermo Gil. 5164 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 28 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 325 records from KU E16 Slæn - Tvinno. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 106 records from Total foraminifera counts of multinet M42/3_MSN1365. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 4085 records from SMNS Palaeontological collection - Tertiary mammals. 78612 records from Stackpole National Nature Reserve Species Inventory and Ad Hoc sightings from around Pembrokeshire. 7 records from Deep-sea ascidians from Papua New Guinea. 1 records from Chaetanaphothrips kiyosumianus (Thysanoptera, Thripidae) new to India with first record of the male. 36188 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 4 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 160 records from Sealife Tracker. 308 records from Censo aéreo de poblaciones de borrego cimarrón (Ovis canadensis cremnobates) en Baja California, México. 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 920 records from Annotated list of observed birds in W and Pendjari Reserves in Benin, February 2010. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 16 records from New records of doryctine wasps (Hymenoptera: Braconidae) from Argentina, with the description of Shawius diiorioi Martínez sp. nov.. 484 records from Biología del murciélago mastín enano (Eumops bonariensis nanus) en Yucatán. 77599 records from Avifauna de la Reserva de la Mariposa Monarca. 121029 records from BMSM Bailey-Matthews National Shell Museum. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 233 records from Föhrenried (Fronreute und Baindt). 820 records from Brood cell No. of trap-nesting species Alb 2008. 1713 records from Seabird observations during long-line fisheries operations in waters south of Tasmania, Australia, 1996-1999. 783 records from Phytoplankton abundance in surface water during cruise CD61. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 6 records from Neolinoptes gen. n., a replacement name for the net-winged beetle genus Linoptes Gorham, 1884 and a new species of Lycomorphon from Guyana (Coleoptera: Lycidae). 8372 records from UWBM Herpetology Collection (Arctos). 240 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-766A. 85 records from Fig 14. Pollen profile from sediment core Schmiecher See. 325 records from Planktic foraminifera abundance of Hole 32-305. 116 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 360 records from Order Araneae. 2 records from Benthic hard-bottom communities abundance at Lilliguapy in 2010. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD13. 5841 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coleoptera_Types_Orient. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 46 records from Antarctic Isopods. 410 records from (Appendix 3) Planktonic foraminiferal composition from ODP Site 172-1056. 4148 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 58 records from Total foraminifera counts of multinet M27/2_MSN882. 59 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1388. 152 records from Abundance of planktic foraminifera at CTD station M39/4_402CTD-55. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_2-CTD16. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD35. 655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 9 records from Coccolith counts of multinet M32/5_MSN982. 14 records from Nannofossil abundance of Hole 8-72A. 7 records from Nannofossil abundance of Hole 9-82A. 4 records from Nannofossil abundance of Hole 52-418. 71 records from Distribution of benthic abyssal gastropods in the Iberian Deep-Sea Basin (Table 2). 2634 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 415 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 593 records from Ostracoda in sediment core PS51/159-10. 2478 records from (Figure 3) Range charts of selected dinoflagellate cysts in ODP Hole 122-762C. 15494 records from (Table 6) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-703A. 907 records from Actualización sistemática y electrónica del acervo de gasterópodos de la Colección Malacológica Dr. Antonio García-Cubas (COMA), del Instituto de Ciencias del Mar y Limnología, UNAM. 3146 records from Inventario de la vegetación acuática vascular de la reserva de la biosfera Pantanos de Centla, Tabasco. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 77 records from Occurrence of recent nannoplankton in sediment core M1_MULT242, Arabian Sea (Fig. 2). 7 records from Nannofossil abundance of Hole 5-33. 5 records from Nannofossil abundance of Hole 84-569. 54 records from (Table 3) Distribution of nannofossils in DSDP Hole 87-583A. 15 records from Microfossil abundance of Hole 59-450. 82 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-699. 14 records from (Table 1) Analyses of coarse fraction of DSDP Hole 94-609. 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 568 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 2586 records from Base de datos y catálogo de helmintos parásitos de anuros de México. 8 records from RISC Non-Native Species Records for Zebra Mussel. 17374 records from Canadian Museum of Nature Amphibian and Reptile Collection - Anura. 19164 records from The Gordon Alexander Orthoptera Collection. 125 records from Artenbestimmung. 3 records from Planktic foraminifera abundance of Hole 54-424B. 164 records from Planktic foraminifera abundance of Hole 94-610B. 462 records from Range table from planktonic foraminifers in ODP Hole 155-942A. 15 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1095B. 1018 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 1 records from Akita Prefectural Museum＋Bryozoans Specimens of Akita Prefectural Museum. 21129 records from Pteridophyta specimens of Shizuoka Prefecture Museum of Natural History. 41548 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 6987 records from Lyman Entomological Museum. 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 3 records from Acari fossil - SMNG. 354 records from Foraminifera distribution of sediment core KS310. 41 records from Altholzparzelle Eilenriede Hannover. 24 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 10 records from Range table from planktonic foraminifers in ODP Hole 169-1038A. 16 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1024. 172 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 1 records from Anagrus nedotepae sp. n. (Hymenoptera: Mymaridae), an egg parasitoid of Nedotepa curta (Hemiptera: Cicadellidae), a pest of coconut palm in West Africa. 152 records from On the genus Trachysalambria Burkenroad, 1934 (Crustacea, Decapoda, Penaeidae), with descriptions of three new species. 11 records from Notes on the Pselaphinae (Coleoptera: Staphylinidae) in Shanghai, China. 1777 records from Museu Paraense Emílio Goeldi - Crustacea Collection. 314 records from Manual para la identificación de lianas en el campo. 42 records from BID-AF2015-0004-NAC - DENOMBREMENT SIMULTANE ET SYNCRONISE DES OISEAUX D’EAU MIGRATEURS AU TOGO. 4598 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1800 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 2544 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 77 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea in 2009. 164357 records from The Himalayan Uplands Plant database (HUP Version 1). 15886 records from Insect Specimen Database of Fukui City Museum of Natural History. 959 records from Black-throated diver national surveys in Scotland. 94 records from Planktic foraminifera abundance of Hole 32-310. 387 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 21 records from Hypostomus rhantos (Siluriformes: Loricariidae), a new species from southern Venezuela.. 19 records from Dinoflagellates, pollen and spore abundance of Hole 29-283. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 287 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 5). 486 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 13 records from Review of the genus Chrysoscota in Cambodia (Lepidoptera, Erebidae, Arctiinae), with description of a new species. 1 records from Pelops fuligineus. 92 records from The Ants of Bulgaria. 16246 records from Herbarium Erlangense. 66 records from A global revision of the Seahorses Hippocampus Rafinesque 1810 (Actinopterygii: Syngnathiformes): Taxonomy and biogeography with recommendations for further research. 135 records from Range table from planktonic foraminifers in ODP Hole 180-1114A. 3130 records from Range table from benthic foraminifers in ODP Hole 154-926A. 187800 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 35517 records from NMSA: Arthropod Collections (1900-2012). 18 records from Redescription of two species of wobbegongs (Chondrichthyes: Orectolobidae) with elevation of Orectolobus halei Whitley 1940 to species level.. 319 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 103 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 3561 records from Sammlung Clemens Borneo Herbarium Hamburgense HBG. 336 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 2978 records from Inventario de los crustáceos decápodos asociados al ecosistema coralino de Pocillopora en el Pacífico tropical mexicano. 292 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 13 records from Two new species of Bradynobaenus Spinola, 1851 (Hymenoptera: Bradynobaenidae) in the semiarid area of Argentina. 56 records from Estetal (Buxtehude). 15 records from Kühnauer Aue und Kühnauer See. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 10404 records from 2005 - Ongoing United Kingdom MarLIN Shore Thing timed search results. 1346 records from Wales Otter Survey Database. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 2509 records from Type Specimen Database of Museum and Institute of Zoology PAS. 29 records from Observations on the Biology of Afrotropical Hesperiidae (Lepidoptera) with particular reference to Kenya. Part 11. Heteropterinae. 44 records from Sistemática molecular de Trogoniformes (Aves): Filogenia del orden y análisis de variabilidad genética de quetzales en la reserva de la Biosfera El Triunfo. 55 records from Galls on Beech Trees in Hainich, 2008. 4 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 1 records from Laubuka parafasciata, a new cyprinid fish species (Teleostei: Cyprinidae) from Mizoram northeastern India. 308 records from Wangerooge. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 15 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 5265 records from Lower Albian, Niveau Paquier range chart of nannofossils in SE France. 2 records from Discovery of a New World ladybird beetle Nephaspis indus Gordon, 1996 (Coleoptera: Coccinellidae: Scymnini) on the Island of Taiwan. 12 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 4748 records from SMDB - Santa Maria Departamento de Biologia. 133 records from Total foraminifera counts of multinet M21/3_MSN676. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 2 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 22 records from Phytoplankton abundance at station Rigel_6_2005-05 in May 2005, Chipana, Chile. 80 records from BB-Biodiversität b. 149 records from Bayerische Donau - Neu Ulm. 238 records from Coccoliths in ODP Hole 104-643A. 3 records from Nannofossil abundance of Hole 9-80. 2 records from Nannofossil abundance of Hole 29-280A. 703 records from Planktic foraminifera counts of sediment core V25-59. 2210 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 149 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 143 records from Akita Prefectural Museum＋Malacostracans Specimens of Akita Prefectural Museum. 4244 records from Insect Specimens of Lake Biwa Museum. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 12 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR72. 3653 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 2984 records from USGS Marine Fishes of St. Croix and U.S. Virgin Islands. 226 records from Range table from benthic foraminifers in ODP Hole 182-1130A. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 233 records from Total foraminifera counts from M35/1_MSN1044. 110 records from Total foraminifera counts of multinet PO247/2_MSN1375. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-10-12. 5 records from A new species of Nanochromis (Teleostei: Cichlidae) from Lake Mai Ndombe, central Congo Basin, Democratic Republic of Congo.. 10 records from Two new butterfly species (Lepidoptera: Rhopalocera) from Mount Cameroon, Gulf of Guinea Highlands, Cameroon. 32 records from Nannofossil abundance of Hole 67-499. 35 records from Ortsrand Zandershagen. 8775 records from (Table 2) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 16 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 14622 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 4 records from Akita Prefectural Museum＋Annelids Specimens of Akita Prefectural Museum. 1 records from Berlese's Primitive Oribatid Mites. 353 records from Stadtgebiet (Dannenberg). 97 records from Occurrence of mammalia relicts at site Rejtek 1. 63 records from GenLink - Genetic diversity of Veronica chamaedrys. 16 records from Abundance of radiolaria at station LV28-3-3. 2238 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 7 records from Range table from planktonic foraminifers in ODP Hole 182-1132A. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 816 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 316 records from Planktic foraminifera counts of sediment core RC11-86. 317 records from Planktic foraminifera counts of sediment core RC14-29. 122 records from Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr).. 1374 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 675 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 34253 records from MedOBIS (EurOBIS). 388 records from SNH Invertebrate Site Condition Monitoring 2013/14: Ben Lomond SSSI. 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 1597 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 18192 records from Plant Specimens of The Shimane Nature Museum of Mt. Sanbe. 6 records from Free-living marine nematodes of Desmodorella and Zalonema (Nematoda: Desmodoridae) with description of two new species from the deep sea of the North Western Pacific. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1400-4. 29 records from Occurrence of mammalia relicts at site la Grotte du Thai. 36 records from Occurrence of mammalia relicts at site Trebacki krs. 60 records from Planktic foraminifera abundance of Hole 19-192. 240 records from Range table from nannofossils in ODP Hole 199-1219A. 1 records from H. Sauter's Formosa-Ausbeute: Formicidae (Hym.).. 4888 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 300 records from A systematic revision of the genus Archocentrus (Perciformes: Cichlidae), with the description of two new genera and six new species.. 31497 records from TWIC Biodiversity Field Trip Data (1995-2014). 24 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171C. 21261 records from Sukkulentensammlung Zürich. 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 3 records from A second species of the genus Blythia Theobald, 1868 (Squamata: Colubridae) from Mizoram, India. 26 records from SNH Invertebrate Site Condition Monitoring 2013/14: Loch Lubnaig Marshes SSSI. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 4 records from Settling the name Diomedea exulans Linnaeus, 1758 for the Wandering Albatross by neotypification. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 180 records from Paul-Gerhardt-Schule Dassel. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN897. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 3 records from Sarcodine counts and carbon biomass at station TT011_15-CTD168. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 49 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Amphipods. 55 records from SNH Invertebrate Site Condition Monitoring 2015: Rinns of Islay SSSI. 92 records from Nottekanal, Klasse 7 - 10. 2 records from List of the specimens of dipterous insects in the collection of the British Museum. 892 records from Weevils of Wales and England. 3 records from A new species of Acantholycosa baltoroi- group (Araneae: Lycosidae, Pardosinae) from the Russian Far East. 53 records from Programa regional para la caracterización y el monitoreo de ecosistemas de manglar del Golfo de México y Caribe Mexicano: Península de Yucatán. 5 records from A new annual fish of the genus Simpsonichthys (Cyprinodontiformes: Cynolebiidae) from the upper Rio Jequitinhonha basin, Brazil. 1 records from Nothrus pulverulentus. 7 records from A new species of Sphelodon Townes (Hymenoptera: Ichneumonidae: Banchinae) from Colombia. 1008 records from Recopilación de datos e información para el Inventario Nacional de Especies de mamíferos marinos nativos de Chile 2016.. 167 records from Water vole survey of Beinn Eighe National Nature Reserve - October 2011. 544 records from Naturalis Biodiversity Center (NL) - Foraminifera. 5850 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 2 records from Two new species of Bungona Harker, 1957 (Ephemeroptera: Baetidae) from Borneo, Indonesia. 5 records from Revision of the coral-inhabiting genus Conopea (Cirripedia: Archaeobalanidae) with description of two new species of the genera Conopea and Acasta. 34 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Minto Craigs SSSI. 5 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 590 records from Fiocruz/COLTRYP - Coleção de Trypanosoma de Mamíferos Silvestres, Domésticos e Vetores. 1298 records from Estudio taxonómico de las aves y mamíferos del Valle Cuatrociénegas, Coahuila, México. 135 records from Waldi-Weiher. 5 records from Fledermäuse u. nachtaktive Insekten. 222 records from SNH Invertebrate Site Condition Monitoring 2013/14: Crathie Wood SSSI. 1 records from Nothrus posticus. 133 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Parulidae. 2 records from First record of Viannaiidae (Nematoda: Trichostrongylina) in fossorial rodents (Ctenomys spp.) from Central Argentina, with description of a new genus and species. 3 records from New data on the taxonomy, ecology, and conservation of the rediscovered Louisea edeaensis (Bott, 1969) (Brachyura: Potamoidea: Potamonautidae), an endangered freshwater crab from Cameroon. 209 records from ZUEC-APL - Coleção de Aplacophora do Museu de Zoologia da UNICAMP. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 268930 records from RECORD Butterfly Data. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 12 records from Revision of the genus Kailasha (Lepidoptera, Erebidae, Arctiinae) from Oriental region, with description of one new species. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 9 records from A new species of Acanthocaudus Smith (Braconidae: Aphidiinae), with a key to species and new host and distribution records for aphidiines associated with Silphium perfoliatum L. (Asterales: Asteraceae). 6 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 7 records from A new genus of the tribe Aemodogryllini (Orthoptera, Rhaphidophoridae, Aemodogryllinae) from China. 100 records from Grenzturm Hohen Neuendorf. 89 records from Birdrace-Team_Wangerooge-Friesland. 28 records from Stadtpark Prinzengarten (Sigmaringen). 40 records from Tiere und Pflanzen um uns herum !. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 85 records from Sedimentological investigation on core V25-45. 122 records from Phytoplankton abundance at station CD46_1005C#4. 7 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 185 records from Abundance of coccosphere-units of site GIK23414. 2 records from Nannofossil abundance of Hole 7-64A. 47 records from Lepidurus arcticus survey Northeast Greenland 2013. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 83 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 175 records from Neißetal. 23 records from Landwehrbach. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 112 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 10552 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 1236 records from Percentages of planktonic foraminifera species in sediment core V30-40. 2989 records from Kelp rafts in the Southern Ocean. 203 records from Planktic foraminifera abundance of Hole 72-515B. 48 records from Benthic foraminifera abundance of Hole 42-380A. 2274 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 10 records from Microzooplankton abundance and biomass at station TT043_21-22. 6 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 1 records from Mamíferos marinos de la Reserva de Biósfera Seaflower. 49 records from (Appendix 1) DSDP Site 94-607A ostracode species census data. 692 records from Collection Trilobita SMF. 1 records from A historical review of the classification of Erebinae (Lepidoptera: Erebidae). 58 records from Lüner Holz (Lüneburg). 5 records from A new monotypic genus, a species synonymy and nomenclatural corrections in the arid-adapted Canthonini (Scarabaeidae, Scarabaeinae) from the Succulent Karoo Biome of south-western Africa. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 1335 records from MCNH Museum of Cultural and Natural History Mammals Collection. 525 records from Benthic foraminifera abundance of Hole 40-360. 1208 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1125. 83 records from Abundance of birds on the channels of Lena Delta in the brood period. 12 records from A new species and new records of Hentzia (Araneae: Salticidae: Dendryphantinae) from the United States. 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 223320 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 73 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1376. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 6 records from Microzooplankton abundance and biomass at station NBP97-08-28-1. 482 records from Kühmark bei Wetzlar. 31 records from Nannofossil abundance of Hole 4-23. 11 records from Benthic macrofauna ab
Keywords: GBIF; biodiversity; species occurrences